Bioinspired superhydrophobic wood: From biomass functionalization to multifunctional applications - Jingjing Liu; Hui Wang; Shuangmin Fu; Ke Pei; Caicai Li; Yushan Yang; Zhiguang Guo (Bioresource Technology, 2026)

The characteristics of environmental parameters and cloud-to-ground lightning of thunderstorm cells in eight regions of South and Inland Plateau in China - Jie Deng; Fengxia Guo; Ke Chen; Qingyuan Wang; Miao He; Hanghang Fu; Yutan Chen (Atmospheric Research, 2026)

Interface-Engineered CeO2/NiFe LDH hierarchical nanoflowers as robust OER catalysts for practical water splitting - Ruiqian Zhang; Yong Luo; Xin Fu; Ceneng Chen; Yanan Wang; Binbin Qian; Ke Xu; Sridhar Komarneni; Xiaoyan Zhang; Guohua Zhong; Kunfeng Chen; Chunlei Yang; et al. (Fuel, 2026)

Fluorine-doped PBA@FPO core-shell structure as bifunctional electrocatalyst for overall water splitting through electronic engineering synergy - Zhiwei Lu; Ke Chen; Rao Fu; Xiangyi Long; Peixin Jiang; Jinrui Wu; Yue Zhang; Yidian Yuan; Qiule Lu; Zhaodan Fu; Minglei Yan; Lan Zhang (Fuel, 2026)

Assessing the cardiovascular toxicity of aspartame: An integrated approach from computational prediction to experimental validation - Qiuhe Chen; Hongjing You; Hecai Wang; Xuanchen Guan; Xiujuan Cen; Lanting Fu; Liang Long; Ke Wang; Yue Xu; Yang Chen (Chemico-Biological Interactions, 2026)

Contrasting droplet size distribution during strong (2020) and weak (2018) Meiyu seasons in the Yangtze-Huaihe River Valley - Ke Yang; Lei Zhong; Shengnan Zhou; Chunguang Cui; Xiaofang Wang; Bin Wang; Yunfei Fu (Atmospheric Research, 2026)

Fungal drivers of mycotoxin contamination in wheat: Early warning and plasma-based control - Keyi Zou; Shujuan Chen; Lin Ji; Guoyan Wu; Ke Zhao; Jingxia Fu; Xiumei Yu; Xiaoxue Shan; Likou Zou (Food Research International, 2026)

The ISChip: A high-throughput qPCR array for absolute quantification of insertion sequences across the One Health continuum - Yanyan Zhou; Wen-Jing Zhong; Xin-Li An; Fu-Yi Huang; Xiao-Yu Guo; Meng-Ke Gao; Mei-Rong Xu; Xu Huang; Hu Li; Bangzhou Zhang; Dirk Springael; Jian-Qiang Su (Environmental Pollution, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Comparative evaluation of fume suppressants for reducing hazardous emissions from asphalt binder: Mechanisms, efficiency, and rheological performance - Feng Ma; Jinshuo Yan; Ke Shi; Zhen Fu; Xinye Jiang; Ruizhe Huang; Shuo Wan; Tianyi Zhang (Transportation Research Part D: Transport and Environment, 2026)

Coupled carbon and nitrogen cycling respond for organic matter enrichment in a transitional setting during the Early Cretaceous global warming - Fei Wang; Xiugen Fu; Shengqiang Zeng; Puyang Ke; Jianquan Yi; Hengye Wei (Journal of Asian Earth Sciences, 2026)

Reemissions of polycyclic aromatic compounds from soil to air in chemical industrial parks - Yousong Zhou; Lu Yu; Kai Xiao; Donglei Fu; Ke Jiang; Jinmu Luo; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2026)

Collagenase-embedded self-healing hyaluronic acid/carboxymethyl chitosan hydrogel with controlled drug release: Boosting chemotherapeutic penetration and efficacy in pancreatic cancer - Jingrong Huang; Jinlin Wu; Yuao Zhang; Yongxia Cui; Ke Yuan; Zihan Zhu; Tao Li; Yun Lu; Kang Xiong; Haowen Pang; Shaozhi Fu (Chemical Engineering Journal, 2026)

Black Soldier Fly Larvae as a Fishmeal Alternative: Effects on Growth, Muscle Quality, Antioxidant Status and Gut Microbiota of Juvenile Pangasius - Jinghua Fu; Jianpeng Li; Ke Zhang; Minjun Xu (Fishes, 2026)
To evaluate the economic and ecological potential of black soldier fly larvae (BSFL) slurry as a fishmeal alternative, 270 juvenile Pangasius (initial body weight: 7.20 ± 0.07 g) were acclimated for two weeks and randomly allocated to three dietary treatments (T0, T1, T2), with three biological replicates per treatment. The feeding trial lasted six weeks (42 days). Fish in T0 were fed the basal diet, while T1 and T2 diets replaced 50% and 100% of fishmeal with BSFL on an isonitrogenous basis, respectively. At trial termination, whole-body proximate composition, muscle texture, and intestinal microbiota were analyzed. BSFL inclusion at 50–100% fishmeal replacement did not compromise growth performance. Moisture and ash content did not differ among treatments (p > 0.05), whereas BSFL supplementation significantly altered muscle texture, reducing hardness and resilience while increasing springiness, chewiness, cohesiveness, and adhesiveness. Both 50% and 100% BSFL replacement enhanced hepatic antioxidant capacity, evidenced by significantly higher superoxide dismutase (SOD) activity (p < 0.05). BSFL also modulated intestinal microbiota and enhanced community evenness, though without significant intergroup differences in bacterial abundance (p > 0.05). This study demonstrated that BSFL could replace 50–100% of fishmeal in diets for juvenile Pangasius, maintaining growth performance while modifying nutritional profiles, muscle texture, hepatic antioxidant status, and intestinal microbiota. Nevertheless, 100% fishmeal replacement triggered distinct shifts in intestinal microbial composition despite satisfactory growth, and the 50% substitution level was, therefore, recommended as a safe proportion for practical aquafeeds.

Diosmetin alleviates retinal ischemia-reperfusion injury through SIRT1-mediated suppression of oxidative stress, inflammation, and PANoptosis - Peng Fu; Xiaobo Wan; Chunrong Zheng; Xiaonian Wu; Ke Xu; Qiuyu Lin; Minli Huang (Immunologic Research, 2026)

Excellent conductivity δ-MnO2/MXene composite as a stable and high‑performance capacitive deionization electrode - Jie Fu; Hui Xu; Yong Ke; Tianxing Tong; Qingbin Chen; Bohuai Liu; Yunyan Wang; Zhumei Sun (Journal of Environmental Chemical Engineering, 2026)

Multi-omics analysis reveals the adaptation strategies of diatoms under high nitrogen-phosphorus ratios: from growth inhibition to reprogramming of metabolic networks - Xinhao Liu; Wanzhen Zhong; Lizhi Zhang; Ke Liu; YuanJie Cui; Weizhang Fu (Journal of Applied Phycology, 2026)

Dimethyl fumarate ameliorates quinolinic acid-induced ageing and neurodegeneration in Caenorhabditis elegans - Yi Sun; Ke Zhou; Jiaorong Cui; Haoxuan Ding; Iqra Shareef; Liuliang Du; Zhen Shi; Linlin Fu; Fenfen Sun; Zuobin Zhu; Wei Pan (Biogerontology, 2026)

Associations of Whole Blood Minerals and Trace Elements with Body Composition in Overweight and Obese Patients: A Retrospective Cross-Sectional Study - Zhiyi Zhou; Jing Chen; Yuanlan Chen; Yiming Fu; Peipei Qi; Yuan Li; Linqiu Ke (Biological Trace Element Research, 2026)

Long-term trends and risk regulation of heat exposure in megacities: seasonal dynamics and determinants - Ziwen Jin; Shuyi Zhang; Ke Zeng; Muyao Ma; Yue Yang; Yuling Fu; Hanxin Tang; Shan Yin; Ji Zheng; Min Liu (Environment, Development and Sustainability, 2026)

Thermal Tolerance of Geographical Populations and Their Hybrids in the Ivory Shell Babylonia areolata - Jingqiang Fu; Linwei Nie; Zhenzhen Cai; Weiguang Zou; Yuan Liang; Wengang Lü; Minghui Shen; Xuan Luo; Weiwei You; Tuanyu Guo; Caihuan Ke (Fishes, 2026)
Global warming and summer heatwaves increasingly threaten the survival of cultured Babylonia areolata, but the heat tolerance of different geographical populations and the potential for genetic improvement by hybridization remain poorly understood. In this study, four geographical populations (Thailand, TL; Wanning, WN; Zhao’an, ZA; Changle, CL) and four hybrid combinations (TH, HT, TF, and FT) were compared for mortality rate, median lethal temperature (LT50), and critical thermal maximum (CTMax) under controlled thermal stress. The results showed that the low-latitude TL population exhibited significantly higher LT50 (36.49 ± 0.05 °C) and CTMax (35.77 ± 0.52 °C) than the high-latitude CL and ZA populations (LT50: 35.90 ± 0.05–36.02 ± 0.04 °C; CTMax: 35.12 ± 0.77–35.26 ± 0.53 °C). All four hybrids had improved heat tolerance compared with their low parents, with TH and HT showing the strongest mid-parent heterosis (e.g., 73.68–78.94% for survival at 36.5 °C). However, none significantly exceeded the high-parent performance (TL), indicating only mid-parent heterosis. These findings reveal significant genetic variation in heat tolerance among geographical populations of B. areolata and confirm that cross-breeding can effectively enhance heat tolerance, though it does not produce transgressive superiority. This study provides key genetic resources and a theoretical basis for breeding heat-tolerant strains of B. areolata.

Extending Zipf's law: hierarchical scaling analysis and the dynamics of city-level CO2 emissions in China - Sen Liang; Ke Wang; Qiu Jin; Jianjun Zhang; Zhenlin Fan; Iskid Jacquet; Bangning Fu (Sustainable Cities and Society, 2026)

Identification of regional groundwater flow systems in geologically complex coalfields using hydrochemical process analysis - Miao Zhang; Luwang Chen; Xiaowei Hou; Yongsheng Hu; Baoxin Zhao; Tianwa Gao; Xianjie Fu; Ke Li; Guoqing Dai (Journal of Hydrology, 2026)

Elucidating soil dissolved organic nitrogen mineralization across soil depths under contrasting fertilizer-application intensities using FT-ICR MS and a two-component model - Ke Yang; Zhuqing Jiang; Hui Peng; Jia Xin; Bo Guo; Zeliang Shen; Yujiao Fu; Tianyuan Zheng (Journal of Hazardous Materials, 2026)

Ecological risk assessment of sediment microplastics in the upper Yellow River: Index applicability and implications for assessment refinement - Ke Fu; Jinge Song; Xinyue Wang; Shengsong Wu; Xiaoyi Liu; Haining Gao; Yong Chen (Journal of Contaminant Hydrology, 2026)

Dual-mode colorimetric and fluorescent pH sensor based on carbon dots for real-time monitoring of shrimp freshness - Ke Zhang; Pingping Wang; Haiming Chen; Chun Chen; Xiong Fu (Food Packaging and Shelf Life, 2026)

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

Sustainability assessment of unmanned aerial vehicles-based last-mile delivery: An integrated life cycle analysis - Xinhui Yang; Yingying Ke; Qianfa Gao; Fu Gu (Environmental Impact Assessment Review, 2026)

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Longitudinal multi-omics unveils rice-fish co-culture promotes common carp health and growth via microbiome remodeling - Chang Fang; Shi-jun Chen; Ke-ni Chen; Nian-nian Zhang; Bing Fu; Shu-ping Zhang; Si-yuan Xiong; Jia-en Zhang; Hui-rong Yang (Aquaculture, 2026)

Corrigendum to “Rapid detection of Streptococcus agalactiae in tilapia using RPA-PfAgo detection systems” [Aquaculture, Volume 619, 30 May 2026, 743875] - Xiaojing Xia; Jiahui Fu; Qianlei Zhu; Kexin Wang; Jingjing Li; Xujie Zhao; Lei Wang; Yanwei Li; Chengshui Liao; Yimin Wang; Yueyu Bai; Yilin Bai; et al. (Aquaculture, 2026)

A comparative study on the developmental toxicity of three dihydroxynaphthalene positional isomers in zebrafish embryos - Zijian Li; Ke Xu; Ziang Wang; Wenhui Zhi; Die Fu; Xiying Zhou; Weitao Hu; Zhonghao Xiao; Zigang Cao; Huimin Li; Xiaowen Shi (Toxicology and Applied Pharmacology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Novel FeWO4@In2O3 Z-scheme heterojunction for enhanced photo-Fenton degradation of water pollutants - Xiaoxiao Li; Ke Song; Weiguang Lv; Han Li; Shengyu Jing; Huagen Liang; Fu Chen; Panagiotis Tsiakaras (Journal of Water Process Engineering, 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Fly ash/natural clay composite monoliths for promising solar interfacial evaporation - Dahao Liu; Ke Zhang; Jie Wang; Yixuan Fu; Zhenxu Li; Lanlan Jiang; Lunxiang Zhang; Yongchen Song; Zheng Ling (Journal of Environmental Chemical Engineering, 2026)

The mechanistic nexus between microplastics and chronic liver disease: A review of current evidence - Shiyun Pu; Changyu Ren; Jiao Liu; Jingyi Zhang; Yan Wang; Ke Fu; Tong Wu (Chemico-Biological Interactions, 2026)

Multistage-enhanced stochastic inverse modeling approach for efficient source characterization of groundwater organic contamination - Zeyu Hou; Yifan Fu; Yingzi Lin; Ke Zhao; Tongzhe Liu; Wenxi Lu (Stochastic Environmental Research and Risk Assessment, 2026)

Association of plasma n-3 polyunsaturated fatty acid with gut mycobiome and implications for glucose homeostasis - Congmei Xiao; Yue Xi; Xinyu Wang; Chang Gao; Ruiqi Shi; Zelei Miao; Yuhui Liang; Wanglong Gou; Ke Zhang; Chun Wang; Xinxiu Liang; Meng Ye; et al. (Science China Life Sciences, 2026)

Rapid detection of Streptococcus agalactiae in tilapia using RPA-PfAgo detection systems - Xiaojing Xia; Jiahui Fu; Qianlei Zhu; Kexin Wang; Jingjing Li; Xujie Zhao; Lei Wang; Yanwei Li; Chengshui Liao; Yimin Wang; Yueyu Bai; Yilin Bai; et al. (Aquaculture, 2026)

Emissions of nitrogen oxide from household gaseous cooking - Yongqiang Zhang; Jian Fu; Tianyao Huang; Jieyang Gao; Hanchen Wang; Ke Jiang; Ran Xing; Guofeng Shen; Shu Tao (Environmental Pollution, 2026)

The toxicity differences of lithium-ion battery cathode materials, lithium iron phosphate (LFP) and lithium cobalt oxide (LCO) to zebrafish(Danio rerio): Mechanisms and environmental impacts - Xinhao Liu; Wanzhen Zhong; Ke Liu; YuanJie Cui; Lizhi Zhang; Weizhang Fu; Luolin Liu (Environmental Pollution, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

Application of Magnetic-Seismic Geophysical Prospecting Technology in Identifying the Carboniferous Volcanic Rocks in the Chepaizi, West Margin of Junggar Basin - Guo-hua Jiao; Wei-ping Zhang; Jin-ke Zhou; Fu-gang Sun; Hai-tao Yang; Man Li; Zhu-qiang Li (Applied Geophysics, 2026)

Safety evaluation of pasteurized Akkermansia muciniphila YGMCC2645 - Jie Tian; Zhili He; Minlei Zhao; Xianghong Ke; Yinjing Zhang; Jingjing Qu; Ying Xia; Shaohua Fu; Wenxiang Yang; Lanjie Pei; Jun Fan; Jianguo Chen; et al. (Food and Chemical Toxicology, 2026)

Seasonal temperature rise influences nitrous oxide and methane accumulation in freshwater habitats via distinctive microbial processes - Teng-Fei Ma; Wen-Ke Liu; Chong-Yang Xing; Ya-Song Chen; Hui-Min Fu; Ji-Chun Bai; Wan Sun; Meng-Meng Liu; Shun-Li Cheng; Meng-Wen Peng (Environmental Pollution, 2026)

Rapid selection of early-maturing and low-ear position maize hybrids suitable for China using genomic prediction - Ping Luo; Wenzhe Li; Lin Zhang; Jie Yang; Houwen Wang; Fei Wang; Ruisi Yang; Xinlong Xu; Ke Yang; Hongjun Yong; Mingshun Li; Jianfeng Weng; et al. (Plant Molecular Biology, 2026)

A Comparative Analysis of GPT-4o and ERNIE Bot in a Chinese Radiation Oncology Exam - Weiping Wang; Jingxuan Fu; Yiming Zhang; Ke Hu (Journal of Cancer Education, 2026)

Utilization of synthetic minority oversampling technique and transfer learning for improving rice and wheat LAI estimation - Ziheng Feng; Ke Wu; Bo Xu; Haiyan Cen; Yuan Zhang; Xiangtai Jiang; Hanyu Xue; Heguang Sun; Hao Yang; Haikuan Feng; Huiling Long; Xingang Xu; et al. (Computers and Electronics in Agriculture, 2026)

Integrative transcriptomic and epigenomic analysis reveals the molecular mechanism of light-enhanced calcification in giant clams - Wenjie Yi; Fan Mao; Ke Wan; Shiwei Fu; Md. Abu Kawsar; Xiangcheng Yuan; Jun Li; Zhiming Xiang; Shu Xiao; Weihua Zhou; Ziniu Yu; Yang Zhang (Aquaculture, 2026)

Soil science research in Research Center for Eco-Environmental Sciences: Review and outlook - Baodong Chen; Zhipeng Hao; Lei Luo; Nan Wu; Wenju Liu; Dong Zhu; Yuan Ge; Weiping Chen; Wentao Jiao; Xin Zhang; Siyi Liu; Jupei Shen; et al. (Journal of Environmental Sciences, 2026)

Nitrogen-phosphorus co-doped carbon layer-confined ultra-thin self-grown polyphase molybdates heterojunction nanosheet arrays for efficient water splitting - Lan Zhang; Rao Fu; Ke Chen; Xi Peng; Li Zhang; Minglei Yan; Chun Wu; Mengmeng Sun; Gehong Su; Yanying Wang; Jianshan Ye; Hanbing Rao; et al. (Fuel, 2026)

Competition release dominates growth recovery of four subtropical broadleaved tree species following an extreme snow event - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Shankar Panthi; Xin-Hua Peng; Ju-Mei Zhang; Pei-Li Fu; Ke-Yan Fang; Ze-Xin Fan (Forest Ecology and Management, 2026)

Effect of roasting on the chemical profiles of white and black sesame seeds during accelerated storage - Hao Liu; Shu-Guang Gao; Ming-Zhe Sun; Mei-Qi Yang; Huai-Yang Cao; Ke-Xin Zhang; Min-Shu Hong; Rui-Fu Cui; Zhao Qin; Hua-Min Liu; Xue-Ya Wang; Zhi-Jie Li (Food Chemistry, 2026)

Structural behaviour and capacity of recycled aggregate concrete-filled stainless steel tubular (RACFSST) columns under eccentric loading - Chengzhang Wu; Jiyang Fu; Zhiwei Yu; Ou Zhao; Ke Jiang; Yukai Zhong (Engineering Structures, 2026)

Dipole-engineered pyridinium iodide passivation for efficient Sn-Pb and all-perovskite tandem solar cells - Ciyu Ge; Chenwei Ni; Qi Xu; Bokai Hao; Wei Ai; Chengjie Deng; Peiyan Zhang; Xinzhi Zu; Hongyan Lu; Zeyu Zhang; Weijun Ke; Haisheng Song; et al. (Chemical Engineering Journal, 2026)

Use of stable nitrogen isotopes in atmospheric aerosol research - Jingqi Bai; Libin Wu; Qingzi Zhao; Ke Xin; Wei Hu; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2026)

Geology and genesis of the Paodaoling intermediate-sulfidation epithermal gold deposit in the Chizhou district, Eastern China - Ke Huang; Guiqing Xie; Zhaoshan Chang; Liuan Duan; Shiqiang Huang; Bin Fu (Mineralium Deposita, 2026)

Molecular crystal memristor-based edge AI platform for energy-efficient and real-time smart grid inspection - Pengfei Guan; Lanhao Qin; Ke Ning; Jie Liu; Decai Ouyang; Yimeng Yu; Jinsong Wu; Xing Lu; Yingshuang Fu; Yuan Li; Huiqiao Li; Tianyou Zhai (Science Bulletin, 2026)

Efficient depolymerization of polyethylene terephthalate fabric under mild conditions and recycling of polyester/cotton blended fabric - Xinping Li; Jinying Fu; Yanyan Guo; Xingyan Wu; Jing Xu; Rongliang Wu; Huaping Wang; Fuyou Ke; Ye Chen (Journal of Environmental Chemical Engineering, 2026)

Selective hydrogenolysis of lignin for sustainable production of 4-propylsyringol over N-doped Ceiba speciosa flower carbon supported Pd catalyst - Shipeng Gu; Wenjun Lei; Yanhuan Ke; Yan Fu; Jie Chang (Journal of Environmental Chemical Engineering, 2026)

Structural characterization and prebiotic activity of oligosaccharides derived from sesame meal produced by different oil extraction methods - Hui-Fang Duan; Xiao-Rong Chen; Ran Zhang; Yuan-Qing Luo; Chang-Yong Lu; Ke-Qing Liu; Rui-Fu Cui; Run-Yang Zhang; Hua-Min Liu (Food Research International, 2026)

A study on fast recognition of multi-class bridge damage based on improved Siamese ResNet50 with limited samples - Liujie Chen; Haodong Yao; Ke Gan; Yingzhuo Ye; Ching-Tai Ng; Jiyang Fu (Engineering Structures, 2026)

Integrated self-powered wearable system for respiratory biomarker detection based on 2D layered conductive composites - Cheng Chen; Zhaorun Tang; Caihong Lv; Donglei Fu; Xianwen Ke; Yuanquan Liu; Liangzhe Chen; Xinghai Liu (Chemical Engineering Journal, 2026)

An electrochemical-photothermal platform driven by DNAzyme walker and HCR on MoS2@ZIF-67 heterojunction substrate for ultrasensitive phytopathogen detection - Bingtao Fu; Yunzhi Ma; Rongshuai Che; Haibo Wang; Yanni Luo; Defen Feng; Ke-Jing Huang; Shengyu Xie (Analytica Chimica Acta, 2026)

Cervical spondylotic myelopathy caused by cervical dystonia: a case report - Shuang Li; Maolin Fu; Yuan Gao; Ke Li; Runnu Jin; Lan Wen (Acta Neurologica Belgica, 2026)

Increased microbial extracellular polymeric substances as a key factor in deep soil organic carbon accumulation - Mengxi Feng; Ming Zhang; Peng Cai; Yichao Wu; Qingling Fu; Xin Zhang; Fei Miao; Wen Xing; Shuiqing Chen; Ke-Qing Xiao; Yong-Guan Zhu (Soil Biology and Biochemistry, 2026)

Enhanced CO2 desorption from monoethanolamine solution using TiO(OH)2-modified diatomite catalyst - Pan Zhang; Zhongfa Zha; Jiawen Yang; Xinbo Wang; Jianwen Song; Shuming Du; Liwen Li; Kun Zhao; Dong Fu; Lemeng Wang; Jun Ke; Pengfei Qu (Process Safety and Environmental Protection, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The Hongjianbingshan W–Li–(Be) deposit in the Beishan Orogenic Belt is not related to carboniferous magmatic–hydrothermal events: Insights from multi-mineral U-Pb and zinnwaldite Rb-Sr geochronology - Yong Yin; Heng-Feng Zhang; Zhuang Duan; Bing-Fei Yu; Heng Luo; Yan-Gang Fu; David R. Lentz; Tao Luo; Ke-Yu Ren; Zhe Ren; Hao Hu (Journal of Geochemical Exploration, 2026)

Carbon and nitrogen cycling in response to global environmental change during the Carnian Pluvial Episode (late Triassic) - Puyang Ke; Xiugen Fu; Qinghua Peng; Hengye Wei; Wei Tang; Wolfgang Ruebsam; Ahmed Mansour; Eva E. Stüeken (Global and Planetary Change, 2026)

Warm-mix rejuvenation effects of waste polyethylene wax and rejuvenator blends on aged asphalt binder - Feng Ma; Ruizhe Huang; Ke Shi; Zhen Fu; Yanxin Jin (Fuel, 2026)

Comparative rheological properties evaluation of virgin and SBS modified-asphalt binder/mastic under solution erosion and its water aging behavior - Feng Ma; Chen Li; Zhen Fu; Jiasheng Dai; Xinye Jiang; Wenhao Dong; Yalu Wen; Ke Shi; Tao Liu; Zhiru Yang; Yao Xue (Fuel, 2026)

Enhancing pearl luster by targeted delivery of astaxanthin using submicron hollow ordered mesoporous silica to the mantle of pearl oysters - Yuan-shuai Fu; Xi-ke Li; Yue Lin; Yun-ao Li; Yong Zhao; Wei-hao Wu; He Wang; Xue-feng Lv; Yuan Zhang; Yong-heng Zhu; Zhi-yi Bai (Chemical Engineering Journal, 2026)

Hybrid nanozyme-natural enzyme catalytic system-based self-powered biosensing platform with dual-signal output for trace-level monitoring of pathogens - Bingtao Fu; Rongshuai Che; Haibo Wang; Yanni Luo; Defen Feng; Jiawen Wu; Jun Yan; Ke-Jing Huang; Xuecai Tan (Chemical Engineering Journal, 2026)

A Deep Ship Trajectory Clustering Method Based on Feature Embedded Representation Learning - Yifei Liu; Zhangsong Shi; Bing Fu; Jiankang Ke; Huihui Xu; Xuan Wang (Journal of Marine Science and Engineering, 2025)
Trajectory clustering is of great significance for identifying behavioral patterns and vessel types of non-cooperative ships. However, existing trajectory clustering methods suffer from limitations in extracting cross-spatiotemporal scale features and modeling the coupling relationship between positional and motion features, which restricts clustering performance. To address this, this study proposes a deep ship trajectory clustering method based on feature embedding representation learning (ERL-DTC). The method designs a Temporal Attention-based Multi-scale feature Aggregation Network (TA-MAN) to achieve dynamic fusion of trajectory features from micro to macro scales. A Dual-feature Self-attention Fusion Encoder (DualSFE) is employed to decouple and jointly represent the spatiotemporal position and motion features of trajectories. A two-stage optimization strategy of “pre-training and joint training” is adopted, combining contrastive loss and clustering loss to jointly constrain the embedding representation learning, ensuring it preserves trajectory similarity relationships while being adapted to the clustering task. Experiments on a public vessel trajectory dataset show that for a four-class task (K = 4), ERL-DTC improves ACC by approximately 14.1% compared to the current best deep clustering method, with NMI and ARI increasing by about 28.9% and 30.2%, respectively. It achieves the highest Silhouette Coefficient (SC) and the lowest Davies-Bouldin Index (DBI), indicating a tighter and more clearly separated cluster structure. Furthermore, its inference efficiency is improved by two orders of magnitude compared to traditional point-matching-based methods, without significantly increasing runtime due to model complexity. Ablation studies and parameter sensitivity analysis further validate the necessity of each module design and the rationality of hyperparameter settings. This research provides an efficient and robust solution for feature learning and clustering of vessel trajectories across spatiotemporal scales.

Geophysical Characteristics and Prospecting Significance of the Halong’erma Polymetallic Deposit in the East Kunlun Metallogenic Belt - You Zhou; Zhi-Qiang Zhang; Ji-En Dong; Hai-Yue Fu; Fa-Long Qi; Wen-ke Fan; Hao Ren; Xue-lin Huang (Applied Geophysics, 2025)

Integrating crop phenology and satellite data for improved nitrogen management in rice farming - Jinpeng Yang; Zhaopeng Fu; Yinshan Wu; Weikang Wang; Jiayi Zhang; Jie Jiang; Ke Zhang; Qiang Cao; Yongchao Tian; Yan Zhu; Weixing Cao; Xiaojun Liu (Computers and Electronics in Agriculture, 2025)

Molecular-scale investigation on the role of MnO2–mediated oxidation in regulating photochemical reactivity of dissolved organic matter - Rui Chai; Huanxin Ma; Hengyi Fu; Ke Sun; Chunhua Feng; Chao Jin; Rongliang Qiu; Shishu Zhu (Water Research, 2025)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Aggregate size mediates the stability and temperature sensitivity of soil organic carbon in response to decadal biochar and straw amendments - Yalan Chen; Yakov Kuzyakov; Qiwen Ma; Zhangliu Du; Ke Sun; Keqing Xiao; Xinru Liang; Yang Li; Yunxian Zhang; Xianqiang Lai; Wei Fu; Bo Gao; et al. (Soil Biology and Biochemistry, 2025)

Water vapor sorption behavior of shale organic matter with various types and maturation - Jiajun Fu; Ke Xu; Yeping Ji; Xuezhe Wang; Yiquan Ma; Mehdi Ostadhassan; Zhejun Pan; Duo Wang; Bo Liu; Yubing Ke; Mengdi Sun (Journal of Hydrology, 2025)

Effects of radio frequency explosion puffing on the texture of purple sweet potato chips and structural properties of pectin under different energy inputs and pressures - Chao Mao; Zhi Chang; Shijing Zhang; Pengfei Ye; Lei Yuan; Xiangwei Chen; Yequn Wang; Hongfei Fu; Yunyang Wang; Ke Wang (Food Research International, 2025)

Effects of radio frequency explosion puffing on the texture of purple sweet potato chips and the physicochemical properties of the flour under different energy inputs and pressures - Chao Mao; Li Zhang; Shijing Zhang; Zhi Chang; Pengfei Ye; Tianshuo Yan; Yequn Wang; Xiangwei Chen; Hongfei Fu; Yunyang Wang; Ke Wang (Food Chemistry, 2025)

High entropy metal organic framework nanozyme with cocktail effect for efficient extraction and colorimetric detection of tetracycline in food and water environment - Lupeng Dou; Sitong Huang; Zhimei Huang; Zhen Liu; Ke Xiao; Leixia Meng; Yamin Fu (Food Chemistry, 2025)

Floc-granule microbial symbiosis drives DNRA in anammox bacteria via cross-feeding for complete autotrophic nitrogen removal - Yulong Yang; Wen-Bo Nie; Xin Tan; Lili Li; Chenhui Yu; Shibo Fu; Ke-Di Peng; Yi Luo; Xiao Ran; Zhihong Zheng; Jin Xu; Jun Li; et al. (Chemical Engineering Journal, 2025)

Enhanced piezoelectric demulsification for high-efficiency separation of water-in-oil (W/O) emulsions based on biomimetic PVDF/liquid metal nanofiber membranes - Wen-Qiang Qiu; Jia-Qi Luo; Qing-Ke Luo; Yan-Ping Zhao; Zhi-Yu Xue; Jing-Song Tang; Hai-Feng Lu; Yi Zhang; Da-Wei Fu (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

On-off-on electrochemiluminescence biosensor with dual-cycle amplification for ultrasensitive prenatal detection of thalassemia mutations using lanthanide europium nanorods - Ya-Qian Xie; Ya-Shu Wei; Hang Du; Yu-Yi Zhou; Lin-Yi Liu; Fu-Cun Wei; Yan-Ni Luo; Xue-Cai Tan; Ke-Jing Huang; De-Fen Feng (Analytica Chimica Acta, 2025)

Research on the application of sulfur-autotrophic denitrifying microorganisms Thiobacillus and Sulfurimonas in wastewater treatment - Dejun Wang; Yanyan Sang; Weizhang Fu; Zongqiang Pang; Wanzhen Zhong; Xinhao Liu; Yuanjie Cui; Lizhi Zhang; Ke Liu; Ziyao Ren (Environment, Development and Sustainability, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Safety evaluation of Nannochloropsis gaditana oil as a novel food - Jingjing Qu; Taiping Zhu; Xiaoya Du; Yingjing Zhang; Jie Tian; Ying Xia; Xianghong Ke; Shaohua Fu; Bolin Fan (Regulatory Toxicology and Pharmacology, 2025)

Study on the coalescence characteristics of oil droplets and molecular mechanism of oil film drainage in alkali-surfactant-polymer flooding produced water - Bin Huang; Hao Chen; Ke Huang; Wei Zhang; Cheng Fu (Process Safety and Environmental Protection, 2025)

Ku proteins play a positive role in the immune response against WSSV infection in Litopenaeus vannamei - Huiling Xing; Wei Xiao; Guoqing Dai; Zhibin Fu; Sheng Ke; Lili Shi (Fish & Shellfish Immunology, 2025)

Aluminum exposure disturbs epigenetic modification and organelle function during early embryo development - Xiao-Ting Yu; Zhen-Hui Fu; Wen-Lin Pan; Yan-Lun Song; Rui-Jie Ma; Hao-Lin Zhang; Xing-He Ke; Shao-Chen Sun; Jun-Li Wang; Lin-Lin Hu (Chemico-Biological Interactions, 2025)

Constraints of in-situ elemental and B isotopic compositions of tourmaline on the origin of the Nong Sua Sn deposit, Thailand - Jie-Hua Yang; Rui-Zhong Hu; Liang Liu; Wei Mao; Ya-Zhou Fu; Mei-Fu Zhou; Heng Chen; Alongkot Fanka; Ke-Jun Hou (Mineralium Deposita, 2025)

Does the cropping system have a substantial influence on greenhouse gas emissions? Dynamics and key factors-based insights from an empirical study of China - Jiongxin Chen; Jianjun Zhang; Shu Fu; Sen Liang; Ke Wang (Agricultural and Forest Meteorology, 2025)

Bivalent vaccination with Edwardsiella tarda and Aeromonas salmonicida protected freshwater fish after challenge and consists a strategic approach against pathogens - Simei He; Guofan Zhang; Yuyuan Peng; Kunyan Li; Jiajie Xie; Ke Zhang; Wen Fu; Yamei Xiao; Liqiu Xia; Shengbiao Hu (Aquaculture, 2025)

Middle Campanian to Maastrichtian foraminifera and biomarkers: Seawater incursion events in the Songliao Basin, Northeast China - Ke-Ying Yue; Sha Li; Tian Jiang; Dang-Peng Xi; Bo-Wen Song; Yu Liang; Li-Xin Sun; Tian-Fu Zhang; Hai-Chun Zhang; Xiao-Qiao Wan; Bo Wang (Palaeoworld, 2025)

Coal fly ash-based Y zeolite modified by ammonium hexafluorosilicate and its enhanced toluene adsorption under high humidity conditions - Sijia Weng; Fanghe Ye; Cha Jing; Xinyang He; Xueyun Zhong; Juntai Tian; Chen Yang; Ke Lei; Haomin Huang; Mingli Fu (Journal of Environmental Chemical Engineering, 2025)

Drainage evolution in response to the growing northeastern Tibetan Plateau: Provenance analysis from drill core of the Jinta Basin (NW China) - Xiaohua Li; Dianbao Chen; Baotian Pan; Eduardo Garzanti; Duo Huang; Ke Wang; Dexuan Chen; Donghong Hu; Wei Liu; Xiangnan Fu (Geomorphology, 2025)

Integrating and mapping spatial heterogeneity of the ecosystem: a novel approach to indicating environmental threats - Xiaojie Wei; Yanan Zhang; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu (Environmental Research, 2025)

Evaluation of real-world CO2 and NOX emissions of various in-use heavy-duty vehicles - Jia Ke; Han Jiang; Xinping Yang; Mingliang Fu; Zhihui Huang; Yunjing Wang; Yan Ding (Journal of Hazardous Materials, 2025)

Exploring the contrasting lake CO2 fluxes and influencing variables in four large shallow subtropical lakes with different hydrological connectivity - Zichun Zhu; Haohao Wu; Ke Jiang; Qitao Xiao; Huawu Wu; Haixia Zhang; Ye Xia; Congsheng Fu (Journal of Environmental Management, 2025)

Mineralogical investigation of modern sediments and source analysis of different grain-size fractions in the middle and lower Yellow River - Dianbao Chen; Wei Liu; Hongli Pang; Xiangnan Fu; Donghong Hu; Ke Wang; Dexuan Chen; Duo Huang; Baotian Pan; Eduardo Garzanti (Geomorphology, 2025)

From fundamental mechanisms to applications and challenges of nanofluid flooding in enhanced oil recovery: A review - Cheng Fu; Ke Huang; Hao Chen; Bin Huang; Wei Zhang (Fuel, 2025)

Genetic gain of yield and agricultural phenotype in foxtail millet from 1970s to 2020s in China - Ke Ma; Zheng Jia; Xinya Wen; Fu Chen (European Journal of Agronomy, 2025)

Effectiveness of governmental and policy initiatives in reducing agricultural greenhouse gas emissions: An empirical analysis of West Africa - Iskid Jacquet; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu; Shidong Liu (Environmental Development, 2025)

Tri-layered immune-competent intestinal chip with synchronous peristaltic-mucosal flow dynamic for Allergenicity assessment of food proteins - Wenjing Zhang; Jiangbing Shuai; Hui Qiu; Xiaofeng Zhang; Ke Li; Jinru Zhou; Huan Li; Linglin Fu (Chemical Engineering Journal, 2025)

Advance and perspective of carbon-based aerogels and their composites - Yanfeng Fu; Hui Ye; Ke Yuan; Qinxin Wang; Longhui Ge; Sheng Cui (Chemical Engineering Journal, 2025)

Protein/polysaccharide composite nanocoating based on amyloid-like aggregation for fresh-cut fruits preservation - Guichen Liu; Rong Liu; Chengyu Fu; Xiang Hu; Ke Li; Luke Yan; Peng Yang; Jian Zhao (Chemical Engineering Journal, 2025)

Combined space cooling/heating and domestic hot water supply driven by data center waste heat: Complementary energy conservation, economic capacity optimization and generic analysis framework - Jun Bai; Xiaohui Wu; Xiaoyuan Chen; Zhiying Zhang; Lin Fu; Chunxiao Zhao; Ke Qing; Qiaoyu Luo; Shirong Gong; Boyang Shen (Building and Environment, 2025)

Analgesic Effects of Acupressure on Jing-jiaji Acupoints in a Rat Model of Cervical Spondylotic Radiculopathy - Shang-Hong Jiang; Song Yang; Ling Meng; Ling-Yao Xie; Jia-Ni Yang; Si-Qi Li; Ke-Ying Liao; Zhi-Fang Qiu; Yao-Yao Xiao; Man-Di Fu; Zhi-Li Liu; Xue-Yu Jiang (Molecular Neurobiology, 2025)

Integrated LC-MS/MS, Network Pharmacology, and Experimental Validation Reveal the Mechanism of Eucommia Ulmoides against Osteoarthritis - Danqing Fu; Chun Gan; Shiyu Gao; Jialu Shu; Shenman Zhou; Ke Zhou; Zhenyan Peng; Haoqiang Dai; Chenjie Xia (Cell Biochemistry and Biophysics, 2025)

Novel one-step solid-state synthesis of 2D Ni/C for efficient electro/photo-catalytic hydrogen evolution - Heng Ke; Yaya Xie; Yi Luo; Yinhong Gao; Lan Yin; Jun Fu; Liangzhe Chen (Fuel, 2025)

Comprehensive evaluation of sulfur content and curing duration effects on the rheological performance of sulfur-extended bitumen - Ke Shi; Feng Ma; Zhen Fu; Baowen Lou; Diego Maria Barbieri; Jiarong Li; Ruimeng Song; Dongdong Yuan (Fuel, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

Assessing the environmental and economic performances of 3D printing processes for manufacturing printed circuit boards - Yingying Ke; Fu Gu; Jingxiang Lv; Jianfeng Guo (Environmental Impact Assessment Review, 2025)

Multi-scale optimization of high-enthalpy encapsulated ternary eutectic phase change materials: Towards sustainable asphalt pavements with enhanced thermal management - Xinye Jiang; Feng Ma; Zhen Fu; Jiasheng Dai; Pengkai Yang; Yingjie Hou; Yan Hao; Yalu Wen; Wenhao Dong; Ke Shi (Chemical Engineering Journal, 2025)

Neurotensin receptor1 signaling promotes progression of epithelial–mesenchymal transition in mice with chronic rhinosinusitis through Wnt3a/β-catenin pathway - Yujie Wu; Xiaoyan Zhu; Hongwei Gu; Feida Fu; Qinghua Guo; Ke Liu; Min Yang; Tian Zhang; Xu Wang (Journal of Molecular Histology, 2025)

Biodegradable Mg–Cu alloy inhibits HBV replication and hepatocellular carcinoma progression - Heyu Zheng; Weiping Zhou; Meiqi Mao; Yiwei Wang; Xing Tian; Biao Yang; Lu Zhao; Shu Li; Ye Sun; Zhongjia Jiang; Ronghua Fan; Yuxin Bai; et al. (BioMetals, 2025)

Numerical investigation of aerated water entry by multiphase Riemann SPH method - Ke Zhao; Sheng-Fa Yang; Pei-Yin Yuan; Fu-Long Shi; Fu-Ren Ming (Ocean Engineering, 2025)

SSRMF: A sparse spectral reconstruction enhanced matched filter for improving point-source methane emission detection in complex terrain - Ke Li; Kaixu Bai; Peng Fu; Penglong Jiao; He Chen; Xinqing Huang; Chaoshun Liu; Ni-Bin Chang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

pH-responsive drug-targeted delivery system: Dual-drug loading hollow mesoporous silica for synergistic therapy bacterial enteritis of Micropterus salmoides - Yuan-shuai Fu; Yue Lin; Wen-jun Zhong; Xing-yu Wang; Xi-ke Li; Yun-ao Li; Sheng-bo Ye; Wen-juan Li; Yong-heng Zhu (Chemical Engineering Journal, 2025)

Meta‐Omics Analysis Reveals Global Distribution of Toxic Pseudo‐nitzschia and Enhanced Neurotoxin Production Under Climate Warming - Dong Xu; Zhuonan Wang; Georgina L. Brennan; Yuqiu Wei; Guanchao Zheng; Qingshan Luan; Xintong Huang; Yanmin Sun; Jia Yang; Xiaowen Zhang; Ke Sun; Xiao Fan; et al. (Global Change Biology, 2025)
The harmful diatom Pseudo‐nitzschia produces the neurotoxin domoic acid (DA), threatening human health and seafood safety in a changing climate. However, global patterns of Pseudo‐nitzschia abundance and the responses of DA production to underlying environmental drivers remain poorly understood, hindering accurate projections of their responses to environmental change. Using global meta‐omics data from Tara Oceans, alongside field survey data from the Chinese coasts and the Southern Ocean, we present the first evidence that four of the most toxic species— Pseudo‐nitzschia multiseries , Pseudo‐nitzschia multistriata , Pseudo‐nitzschia delicatissima , and Pseudo‐nitzschia pungens —are prevalent not only in coastal ecosystems but also in open ocean environments, spanning from pole to pole. We identify rising temperatures are recognized as a key driver of Pseudo‐nitzschia 's spatial distribution, DA production, and biosynthetic metabolism. Global models suggest that by 2100, under the SSP2‐4.5 climate scenario, the abundance of P. multiseries will increase by approximately 75.4%, while toxin production will be even more significantly enhanced, rising by up to 200.4%. This study significantly expands the known global distribution of these neurotoxin‐producing diatoms and predicts their increasing prevalence and toxicity under future global changes.

Synergistic bimolecular erosion-healing interfacial passivation for wide-bandgap perovskite and tandem solar cells - Shiqiang Fu; Guang Li; Shun Zhou; Jiahao Wang; Dexin Pu; Lishuai Huang; Zhiqiu Yu; Wanping Chen; Guojia Fang; Weijun Ke (Science Bulletin, 2025)

Response of ecological condition in ecologically fragile areas to disturbance from extreme precipitation event: An empirical analysis from the loess plateau - Kexin Yi; Jianjun Zhang; Haoyi Lei; Wei Chen; Yaping Zhang; Shu Fu; Ke Wang (Journal of Cleaner Production, 2025)

New insights on desulfurization mechanism of sulfur-containing phases during iron pellet oxidation: Constraints and mitigation strategies - Ke Ma; Jing Yi; Zijian Su; Xiaoguang Bai; Guowei Fu; Tao Jiang; Yuanbo Zhang (Journal of Environmental Chemical Engineering, 2025)

Tuning electron density of NiFe alloy by iron and Ti4+ in mesoporous TS-1 zeolite for selective hydrogenation of fatty acids into alcohols or alkanes - Mingyu Huang; Wenqian Fu; Lei Zhang; Liqin Wu; Jialiang Ke; Tiandi Tang (Fuel, 2025)

Improving the quality of frozen steamed stuffed buns after freeze-thaw cycles: Synergistic effects of cellulase, xylanase and sourdough - Zhao-Qiu Fu; Xiao-Hong Sun; Ke-Xue Zhu; Xiao-Na Guo (Food Bioscience, 2025)

Dual redox-active sites with synergistic spin polarization effect to facilitate overall CO2 photoreduction with H2O - Xiaoyan Zhang; Wenkang Ni; Peihang He; Zhijie Wang; Ke Wang; Zizhong Zhang; Wenxin Dai; Xianzhi Fu (Chemical Engineering Journal, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Genetic assessment of feed efficiency in the spotted Babylon Babylonia areolata - Linwei Nie; Yijie Kong; Ziyi Ma; Jingqiang Fu; Shengtai Liu; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2025)

Dissipation of Ulva prolifera green tides across various spatial and temporal scales and the short-term effects on marine environments - Jiacheng Sun; Ke Liu; Haibo Zhang; Jie Fu; Xiaoyong Shi; Ziwei Yao; Gang Zhao; Zhenxia Sha; Hao Cui; Jinpeng Wu (Marine Environmental Research, 2025)

Changes in the grain quality of foxtail millet released in China from the 1970s to the 2020s - Ke Ma; Xiangyang Yuan; Zheng Jia; Huayu Lu; Xiangyang Chen; Xinya Wen; Fu Chen (Food Research International, 2025)

A critical review of human internal exposure to short-chain chlorinated paraffins and its concerning health risks - Ke Fang; Yi-bin Sun; Run-ming He; Jian-kun Qian; Wen Gu; Yi-fu Lu; Zhao-min Dong; Yi Wan; Chao Wang; Song Tang (Environmental Research, 2025)

Electrospun sodium titanate-MXene/carbon nanofibers as binder-free electrode for enhanced hybrid capacitive deionization - Xin Li; Xiang Fu; Youfang Zhang; Qunchao Zhang; Zhaoyang Wei; Ke Wang; Robert K.Y. Li; Dean Shi; Jun Jin (Chemical Engineering Journal, 2025)

Chlorpyrifos-oxon results in autophagic flux dysfunction contributing to neuronal apoptosis via a ROS/AMPK/CHOP activation pathway - Jui-Ming Liu; Kuan-I Lee; Chin-Chuan Su; Kai-Min Fang; Shing-Hwa Liu; Shih-Chang Fu; Chun-Ying Kuo; Kai-Chih Chang; Jun-An Ke; Ya-Wen Chen; Ching-Yao Yang; Chun-Fa Huang (Chemico-Biological Interactions, 2025)

Relative phase between tidal and solar cycles influences the heating of a coral atoll lagoon - Sarah Ruth Merrigan; Geno Pawlak; Gregory Sinnett; Ke‐Hsien Fu; Kristen A. Davis (Limnology and Oceanography, 2025)
We seek to understand the physical processes driving a recent warming event in Dongsha Atoll lagoon, a coral atoll in the South China Sea. The system has experienced hypoxia‐related fish kills and seagrass die‐offs, further motivating our understanding of circulation and exchange within the lagoon. Hydrographic observations were collected in summer 2019 to examine circulation and ocean–lagoon exchange. A heat budget was constructed to investigate the relative influence of tides, wind, waves, surface heating, and advective ocean–lagoon exchange on the lagoon heat content. Volume fluxes also allow for the estimate of bulk lagoon flushing time, which is critical in driving water temperatures, biogeochemical cycles, and reef ecosystem functions. Over the 22‐d study period, the lagoon warmed by 1.5°C, driven primarily by solar radiative heating. Surface heat fluxes were balanced by cooling from advective exchange through deeper channels and over the shallow reef flat surrounding the lagoon. Without these cooling flows, the lagoon would have heated by 4.5°C over the study period. Estimated flushing times for the Dongsha Atoll lagoon range from 4.6 to 6.1 d for spring and neap tide. A phase‐locked interaction between the diurnal solar cycle and the diurnal tide drives advective cooling over the reef flat into the lagoon at night during the summer, especially during spring tide. These results highlight a unique mechanism shaping seasonal patterns in circulation and heat fluxes in a diurnal‐tide‐dominated reef system, which is likely important for other biogeochemical parameters and in shallow coastal ecosystems with similar tidal forcing.

Identification and characterization of Colletotrichum camelliae, the causal agent of leaf spot of Polygonatum odoratum in China - Rui Zhang; Yiyi Feng; Chun Wu; Ke He; Shaming Fu; Cheng Li (Crop Protection, 2025)

Based on metabolomics and fourier transforms near infrared spectroscopy characterization of Lanxangia tsaoko chemical profile differences among fruit types and development of rapid identification and nutrient prediction models - Deng-Ke Fu; Wei-Ze Yang; Mei-Quan Yang; Tian-Mei Yang; Yuan-Zhong Wang; Jin-Yu Zhang (Food Bioscience, 2025)

Long-term N fertilization increases water use and use-efficiency of winter wheat - Yuhao Yang; Jun Zou; Biao Feng; Suya Hu; Bowen Qiao; Wenhai Huang; Li Zhang; Haoyu Zheng; Matthew Tom Harrison; Ke Liu; Xinya Wen; Fu Chen; et al. (Field Crops Research, 2025)

The grain coarsening principle and the surface degradation mechanism of single-crystalline LiNi1-x-yCoxMnyO2 in lithium-ion batteries prepared by the flux-assisted method - Yinjia Zhang; Zhichen Xue; Guorong Hu; Weigang Wang; Yanbing Cao; Zhongdong Peng; Xiangdong Zhu; Quanjun Fu; Ke Du (Chemical Engineering Journal, 2025)

Highly effective adsorption, porous and charged CAP@Ui0-66-NH2@PPy hybrid fibrous membrane based on MOFs for Cr (VI) removal from wastewater - Tiantian Li; Zhining Huang; Mengfan Hu; Yuen Hu; Ke Quan; Man Zhou; Yao chen; Shaoju Fu (Chemical Engineering Journal, 2025)

Correction to: Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

Organic Matter Occurrence and Its Effects on Pore Structure and Methane Adsorption Capacity: A Case Study of the Niutitang Black Shale in Guizhou, China - Peng Xia; Fang Hao; Jinqiang Tian; Yong Fu; Yuliang Mou; Chuan Guo; Zhen Yang; Ke Wang (Journal of Earth Science, 2025)

Flame-retardant effect of scalable all clay composite films - Yixuan Fu; Zhaoyi Wang; Huiquan Liu; Ke Zhang; Lunxiang Zhang; Yongchen Song; Peng Wu; Yanghui Li; Zheng Ling (Applied Clay Science, 2025)

Delayed Detached-Eddy Simulations of Aerodynamic Variability During Carrier-Based Aircraft Landing with a Domain Precursor Inflow Method - Jiawei Fu; Ruifan Hu; Hong Wang; Ke Xu; Shuling Tian (Journal of Marine Science and Engineering, 2025)
Flight tests and wind tunnel experiments face difficulties in investigating the impact of aircraft carrier air-wake on the landing process. Meanwhile, numerical methods generally exhibit low overall computational efficiency in solving such problems. To address the computational challenges posed by the disparate spatiotemporal scales of the ship air-wake and aircraft motion, a domain precursor inflow method is developed to efficiently generate unsteady inflow boundary conditions from precomputed full-domain air-wake simulations. This study investigates the aerodynamic variability of carrier-based aircraft during landing through the turbulent air-wake generated by an aircraft carrier, employing a hybrid RANS-LES methodology on dynamic unstructured overset grids. The numerical framework integrates a delayed detached-eddy simulation (DDES) model with a parallel dynamic overset grid approach, enabling high-fidelity simulations of coupled aircraft carrier interactions. Validation confirms the accuracy of the precursor inflow method in reproducing air-wake characteristics and aerodynamic loads compared to full-domain simulations. Parametric analyses of 15 distinct landing trajectories reveal significant aerodynamic variability, particularly within 250 m of the carrier, where interactions with island-generated vortices induce fluctuations in lift (up to 25%), drag (18%), and pitching moments (30%). Ground effects near the deck further amplify load variations, while lateral deviations in landing paths generate asymmetric forces and moments. The proposed methodology demonstrates computational efficiency for multi-scenario analysis, providing critical insights into aerodynamic uncertainties during carrier operations.

Development of a sex-specific molecular marker reveals the ZW/ZZ sex-determination system in Babylonia areolata (link 1807) - Yu Zou; Yuan Liang; Xuan Luo; Weiwei You; Minghui Shen; Jingqiang Fu; Caihuan Ke (Aquaculture, 2025)

Measuring heat transfer index (HTI): A new method to quantify the spatial influence of land surface temperature between adjacent urban spaces - Wei Chen; Jianjun Zhang; Chenyan Huang; Shu Fu; Sen Liang; Ke Wang (Sustainable Cities and Society, 2025)

Experimental comparison of air entrapment capacity in sandy soils for liquefaction mitigation: Evaluating air injection method efficiency in soil desaturation - Saeed Sarajpoor; Yumin Chen; Yi Han; Runze Chen; Zhongling Fu; Ke Ma (Soil Dynamics and Earthquake Engineering, 2025)

Genetic analyses reveal wildfire particulates as environmental pollutants rather than nutrient sources for corals - Ke Liu; Bo Qin; Ruoxing Hao; Xiaoyan Chen; Yu Zhou; Wenqian Zhang; Yichen Fu; Kefu Yu (Journal of Hazardous Materials, 2025)

Altered precipitation affects soil enzyme activity related to nitrogen and phosphorous but not carbon cycling: A meta-analysis - Xiaowei Liu; Qing Bai; Ke Liang; Mengting Pei; Ji Chen; Biao Zhu; Qiang Yu; Changhui Peng; Fu Xing; Liang Guo (Journal of Environmental Management, 2025)

Social conditions alter the growth, metabolic rate, behavioral traits, and food-shelter preferences in the juvenile qingbo Spinibarbus sinensis - Yu-Lin Zhang; Wen-Qian Zhou; Shi-Jian Fu; Lauren E. Nadler; Shaun S. Killen; Ke-Ying Zhou; Shi-Long Zheng; Cheng Fu (Behavioral Ecology and Sociobiology, 2025)

A multitemporal remote sensing thick cloud removal network based on implicit reconstruction - Ke Zhang; Han Nie; Weitong Li; Jianxin Wang; Bo-Hui Tang; Leiguang Wang; Zhitao Fu (International Journal of Remote Sensing, 2025)

Exploring water quality variations and biofilm growth in a drinking water distribution system via a biofilm annular reactor series system and predictive modelling of residual chlorine - Zhong Sheng Tai; Yuanpeng Sun; Carl Angelo Dulatre Medriano; Yuyao Fu; Yuyang Jiang; Fengyuan Lei; Ke Liu; Tianyu Yan; Lee Jie Xin Eve; Sung Woo Bae; Quek Puay Hoon Elaine; Phen Wei Chue; et al. (Chemosphere, 2025)

Effects of dietary resveratrol supplementation on the growth performance, physiological health, transcriptomic response, and intestinal microflora of Litopenaeus vannamei - Zhibin Fu; Jian Chen; Hang Yuan; Yudong Zheng; Gongyu Li; Sheng Ke; Shuang Zhang; Lili Shi (Aquaculture, 2025)

Selective oxidation of nitrogenous heterocyclic compounds by heat/peroxymonosulfate in phenol-rich wastewater - Liangjie Wang; Zhengyi Sun; Jinrui Shi; Han Li; Tao Fu; Yi Xu; Ke Xiao; Huazhang Zhao (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Low-temperature oxidative pyrolysis characteristics of tobacco components - Zhongya Guo; Ke Zhang; Huanwei Li; Lili Fu; Qi Zhang; Ze Liu; Le Wang; Xueyi Qiao; Heng Guo; Ran Chen; Bing Wang; Bin Li (Biomass and Bioenergy, 2025)

Source characteristics and quantitative estimates of organic carbon composition in the intertidal zones of Jiaozhou Bay, China - Ke Liu; Jie Fu; Li Li; Daolai Zhang; Xiaotong Xiao (Marine Pollution Bulletin, 2025)

Profiling of chromatin accessibility and regulatory elements toward understanding the mechanisms underlying growth regulation in the Pacific oyster (Crassostrea gigas) - Ke Wan; Chenyu Shi; Yongjing Li; Liting Ren; Huiru Fu; Qi Li; Shikai Liu (Aquaculture, 2025)

Tetrabromobisphenol A induced p38-MAPK/AMPKα activation downstream-triggered CHOP signal contributing to neuronal apoptosis and death - Jui-Ming Liu; Shing-Hwa Liu; Shih-Chang Fu; Wei-Cheng Lai; Kai-Min Fang; Ken-An Lin; Jun-An Ke; Chun-Ying Kuo; Chin-Chuan Su; Ya-Wen Chen (Toxicology, 2025)

Inoculation of thermophilic bacteria from giant panda feces into cattle manure reduces gas emissions and decreases resistance gene prevalence in short-term composting - Jingxia Fu; Shujuan Chen; Yulan Tan; Keyi Zou; Xiumei Yu; Lin Ji; Jianmin Zhang; Xingning Xiao; Wen Wang; Ke Zhao; Likou Zou (Journal of Environmental Management, 2025)

The exploration of pasteurization processes and mechanisms of inactivation of Bacillus cereus ATCC 14579 using radio frequency energy - Yanan Sun; Yiming Jia; Ke Wang; Songlei Wang; Baozhong Cui; Chao Mao; Xiaoying Guo; Yuxin Feng; Hongfei Fu; Xiangwei Chen; Yequn Wang; Zhenna Zhang; et al. (International Journal of Food Microbiology, 2025)

Safety evaluation of alpha-glycerylphosphorylcholine as a novel food - Jie Tian; Xianghong Ke; Yinjing Zhang; Jingjing Qu; Shaohua Fu; Ying Xia; Wenxiang Yang; Yanhua Zeng; Jun Fan; Yanmei Li; Bolin Fan (Food and Chemical Toxicology, 2025)

Cassiterite geochronology and geochemistry of the Yunling Sn deposit: implication for late Cenozoic mineralization in western Yunnan, China - Ke Xiao; Xiang Sun; Rongqing Zhang; Mingjun Zheng; Tong Pei; Pete Hollings; Bin Fu; Jun Deng (Mineralium Deposita, 2025)

Metabolic engineering of Escherichia coli for upcycling of polyethylene terephthalate waste to vanillin - Yang Li; Xiao-Min Zhao; Si-Qi Chen; Zhao-Yuan Zhang; Qi-Sheng Fu; Shu-Min Chen; Sheng Chen; Jing Wu; Ke-Wei Xu; Ling-Qia Su; Zheng-Fei Yan (Science of The Total Environment, 2024)

Effect of pipe material and wall thickness on descaling effect for bubble flow pipes based on leaky ultrasonic guided wave - Zhigang Qu; Song Shen; Yunkun Fu; Yingnan Liu; Liqun Wu; Quanpeng Zhang; Yang An; Ke Zhang (Process Safety and Environmental Protection, 2024)

Occurrence and fate of five representative neonicotinoid insecticides across different wastewater treatment plants and the impact on receiving water bodies - Yuhan Ke; Wanbing Zheng; Di Tian; Siyu Ke; Shuna Fu; Zhe Zhang; Yue Xie; Junyu Zhu; Bangxing Ren; Chao Zhang; Xiaohui Yi; Mingzhi Huang (Environmental Research, 2024)

Environmental Persistent Free Radicals in highly polluted soils and the association with polycyclic aromatic compounds - Yongqiang Zhang; Yousong Zhou; Hanchen Wang; Kai Xiao; Zhihan Luo; Yaojie Li; Ran Xing; Ke Jiang; Donglei Fu; Wenxin Liu; Shu Tao; Guofeng Shen (Environmental Research, 2024)

Whether hypoxia tolerance improved after short-term fasting is closely related to phylogeny but not to foraging mode in freshwater fish species - Ke-Ren Huang; Qian-Ying Liu; Yong-Fei Zhang; Yu-Lian Luo; Cheng Fu; Xu Pang; Shi-Jian Fu (Journal of Comparative Physiology B, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

Blue room-temperature phosphorescent carbon dot composites with high quantum yield for information encryption and LED light emission - Shaowen Yang; Hongmei Zhang; Ke Jian; Liming Fu; Di Lan; Xihui Zhao (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cytotoxic steroidal glycosides from Paris rugosa rhizomes - Jian-Ke Jia; Jun Yang; Xing-Zhi Yang; Ji-Feng Luo; Xiao-Yan Duan; Ying-Li Yang; Jin-Fu Wan; Yue-Hu Wang (Phytochemistry Letters, 2024)

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

In-situ dual-MOF functionalized quasi-fractal networks with Janus wettability for high-efficient fog harvesting and intelligent interface materials - Yongshen Zhou; Shuangmin Fu; Shulun Ai; Ke Pei; Zhiguang Guo (Chemical Engineering Journal, 2024)

Enhanced electrochemical cyclability of composite sodium metal anode with inorganic-rich solid electrolyte interphase - Changqun Cen; Xiaoxue Yang; Xiancheng Wang; Lin Fu; Yuanjian Li; Ke Lu; Liqing He; Yongming Sun (Chemical Engineering Journal, 2024)

Organosilica with tunable pore structure and antibacterial activity for intelligent humidity control - Jin-Wei Liu; Tao Fu; Yang He; Liang-Jie Wang; Ke-Ren Ding; Hua-Zhang Zhao (Chemical Engineering Journal, 2024)

Targeting m6A mRNA demethylase FTO alleviates manganese-induced cognitive memory deficits in mice - Yi Wen; Zhushan Fu; Jiashuo Li; Mingyue Liu; Xinmiao Wang; Jingqi Chen; Yue Chen; Haocheng Wang; Sihang Wen; Ke Zhang; Yu Deng (Journal of Hazardous Materials, 2024)

Corrigendum to ““One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection” [Chem. Eng. J. 457 (2023) 140997] - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Triggering Receptor Expressed on Myeloid Cells 2 Alleviated Sevoflurane-Induced Developmental Neurotoxicity via Microglial Pruning of Dendritic Spines in the CA1 Region of the Hippocampus - Li Deng; Shao-Yong Song; Wei-Ming Zhao; Xiao-Wen Meng; Hong Liu; Qing Zheng; Ke Peng; Fu-Hai Ji (Neuroscience Bulletin, 2024)

Recent advances and prospects of neonicotinoid insecticides removal from aquatic environments using biochar: Adsorption and degradation mechanisms - Song Cui; Jialin Lv; Rupert Hough; Qiang Fu; LiHui An; Zulin Zhang; Yuxin Ke; Zhikun Liu; Yi-Fan Li (Science of The Total Environment, 2024)

Improved permeability in ceramsite@powdered activated carbon (PAC)-MnOx coupled gravity-driven ceramic membrane (GDCM) for manganese and ammonia nitrogen removal with intermittent short-term vertical aeration - Wei Song; Zhitian Peng; Jiawan Li; Xiaokai Wang; Caixia Fu; Xing Du; Ke Kuang; Ziyuan Wang; Zhihong Wang; Zhiwei Zhao (Journal of Hazardous Materials, 2024)

Investigation of the cohesive behavior of water-intervened rejuvenated SBS-modified bitumen - Ke Shi; Feng Ma; Zhen Fu; Jenny Liu; Ruimeng Song; Dongdong Yuan; Yujie Tang (Journal of Cleaner Production, 2024)

Dynamic changes of key metabolites in Longjing green tea during processing revealed by widely targeted metabolomic profiling and sensory experiments - Lin Zeng; Yan-Qing Fu; Ying Gao; Fang Wang; Shuang Liang; Jun-Feng Yin; Marie-Laure Fauconnier; Lijing Ke; Yong-Quan Xu (Food Chemistry, 2024)

Flow pattern and pressure loss of foam flow in horizontal pipes: Role of surfactant type and dynamic surface tension - Huan Li; Zhihao Fu; Xiaoyang Yu; Yuqing Song; Ke Qiu; Shouxiang Lu (Chemical Engineering Journal, 2024)

Modulating d-orbital electronic configuration of PtRu via charge donation from Co-enriched core boosts methanol electrooxidation - Zhaohong Li; Shiyu Ke; Xingqun Zheng; Yihan Huang; Wensheng Fu; Yi Wang; Yao Nie (Chemical Engineering Journal, 2024)

The emerging and legacy persistent organic contaminants in corals of the South China Sea - Yao-Wen Qiu; Jun Li; Mei-Xia Zhao; Ke-Fu Yu; Gan Zhang (Chemosphere, 2024)

Studies of the diluent, temperature and pressure effect on the lower and upper flammability limits of ammonia in air - Wen Fu; Yulong Zhou; Jiangtao Wu; Ke Zhang; Xianyang Meng (Process Safety and Environmental Protection, 2024)

Inhibition of flowering by gibberellins in the woody plant Jatropha curcas is restored by overexpression of JcFT - Ping Huang; Jie Yang; Jiapeng Ke; Li Cai; Yingxiong Hu; Jun Ni; Chaoqiong Li; Zeng-Fu Xu; Mingyong Tang (Plant Science, 2024)

Molecular composition and sources of free amino acids in atmospheric aerosols from Mt. Tai and a nearby city - Qingzi Zhao; Libin Wu; Xiaoli Fu; Wei Hu; Yajie Wang; Yuantao Wang; Ke Xin; Jingjing Meng; Siyao Yue; Junjun Deng; Pingqing Fu (Atmospheric Environment, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Composting of invasive plants in urban watercourses and its application in riverbanks: mechanisms and compost quality assessment - Peiyin Wang; Guiping Fu; Zhipeng Guo; Lin Zhao; Weicheng Pang; Chao Pan; Ke Wang; Qiqi Wu; Yurou Chen (Journal of Soils and Sediments, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

CXCL1/IGHG1 signaling enhances crosstalk between tumor cells and tumor-associated macrophages to promote MC-LR-induced colorectal cancer progression - Lingqiao Wang; Weiyan Chen; Huidong Jin; Yao Tan; Chengwei Guo; Wenjuan Fu; Zhiling Wu; Ke Cui; Yiqi Wang; Zhiqun Qiu; Guowei Zhang; Wenbin Liu; et al. (Environmental Pollution, 2024)

Disruption of PABPN1 phase separation by SNRPD2 drives colorectal cancer cell proliferation and migration through promoting alternative polyadenylation of CTNNBIP1 - Zhijie Hu; Mengxia Li; Yufeng Chen; Liutao Chen; Yuting Han; Chengyong Chen; Xin Lu; Nan You; Yawen Lou; Yingye Huang; Zhanfeng Huo; Chao Liu; et al. (Science China Life Sciences, 2024)

Reactive Oxygen Species-Mediated Mitophagy and Cell Apoptosis are Involved in the Toxicity of Aluminum Chloride Exposure in GC-2spd - Hui- xin Peng; Fu Chai; Ke-heng Chen; Yan-xin Huang; Guang-ji Wei; Huixiong Yuan; Yan-fang Pang; Shi-hua Luo; Chun-fang Wang; Wen-cheng Chen (Biological Trace Element Research, 2024)

DPP8/9 inhibition attenuates the TGF-β1-induced excessive deposition of extracellular matrix (ECM) in human mesangial cells via Smad and Akt signaling pathways - Ke Li; Yuzhan Zhang; Weihao Zhao; Rongrong Wang; Yan Li; Linting Wei; Li Wang; Xianghui Chen; Zhao Chen; Pengfei Liu; Na Nie; Xuefei Tian; et al. (Toxicology Letters, 2024)

Freezing pre-treatment improves radio frequency explosion puffing (RFEP) quality by altering the cellular structure of purple sweet potato [Ipomoea batatas (L) Lam.] - Chao Mao; Yurui Chen; Tong Liu; Pengfei Ye; Yequn Wang; Xiangwei Chen; Hongfei Fu; Yunyang Wang; Ke Wang (Food Research International, 2024)

Rational design of a rapidly responsive and highly selective fluorescent probe for SO2 derivatives detection and imaging - Shiyi Zhang; Xiaopeng Yang; Ying Xu; Haiyang Wang; Fei Luo; Guangming Fu; Dingwei Yan; Miao Lai; Yu Ke; Yong Ye; Xiaoming Ji (Food Chemistry, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

Survival and immune responses of two populations of Babylonia areolata and their hybrids under pathogenic Vibrio challenge - Jingqiang Fu; Yuan Liang; Minghui Shen; Wengang Lü; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2024)

Effect of anions on sonochemical degradation of PPCPs and their DBPs formation potential - Yu-qiong Gao; Ke-xuan Li; Qian Zeng; Fu-xiang Tian; Ze-ning Fan; Gang-yi Xing; Nai-yun Gao (Journal of Water Process Engineering, 2024)

Dual purpose ratooned rice improves agri-food production with reduced environmental cost - Deqiang Qi; Ke Liu; Mingfang Fu; Matthew Tom Harrison; Xiaofei Shi; Xiangchen Liu; Peter de Voil; Yunbo Zhang; Ando Radanielson; Wenge Wu; Jingrui Chen; Yu Jiang; et al. (Journal of Cleaner Production, 2024)

Foliar application of selenium promotes starch content accumulation and quality enhancement in foxtail millet grains - Xiangyang Chen; Xiangyu Li; Zecheng Zhang; Chu Wang; Yiwei Li; Huayu Lu; Ke Ma; Zhenzhen Gao; Xiaogang Yin; Fu Chen; Xinya Wen (Field Crops Research, 2024)

Selenium binding protein 1 protects renal tubular epithelial cells from ferroptosis by upregulating glutathione peroxidase 4 - Weihao Zhao; David J. Nikolic-Paterson; Ke Li; Yan Li; Yinhong Wang; Xianghui Chen; Zhaoyang Duan; Yuzhan Zhang; Pengfei Liu; Shemin Lu; Rongguo Fu; Lifang Tian (Chemico-Biological Interactions, 2024)

Diterpenoid alkaloids with chemotaxonomic significance from Aconitum polycarpum - Lin Chen; Jie Wen; Jia-Yi Ma; Ke Xu; Cheng-En Fu; Wen-Cheng Liang; Chen-Ying Zhu; Jin-Qiu Wang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2024)

Polycyclic aromatic compounds (PACs) in industrial soils from northwestern of China: occurrence, distribution, exposure risk, and implications on risk-based controls - Yousong Zhou; Kai Xiao; Yongqiang Zhang; Donglei Fu; Ke Jiang; Jinmu Luo; Yuancheng Li; Guofeng Shen; Wenxin Liu; Shu Tao; Senlin Lu (Environmental Geochemistry and Health, 2024)

Sandwich assay for β-lactoglobulin in infant food formula based on a hierarchically architectured antifouling capture probe and fluorescent recognition probe - Huan Li; Donghui Jia; Jiangbing Shuai; Xiaofeng Zhang; Shunyu Wang; Min Wang; Ke Li; Linglin Fu (Food Chemistry, 2024)

Flutter control optimization for a 5000 m suspension bridge with active aerodynamic flaps: a CFD-enabled strategy - Zilong Wang; Lin Zhao; Yiheng Fu; Genshen Fang; Wei Cui; Ke Li; Yaojun Ge (Engineering Structures, 2024)

Thermal performance and ventilation analysis of a zigzag Trombe wall: Full numerical and experimental investigations - Hong-Liang Zhang; Bin Li; Dun-Ke Shi; Wei-Wei Wang; Fu-Yun Zhao (Energy and Buildings, 2024)

Assessing shallow slope stability using electrical conductivity data and soil hydraulic characteristics - Ya-Sin Yang; Hsin-Fu Yeh; Chien-Chung Ke; Lun-Wei Wei (Engineering Geology, 2024)

Retrievable ultrafast covalent triazine framework membranes for organic solvent nanofiltration - Guiliang Li; Yang Liu; Zhaoyi He; Ke Shi; Fu Liu (Chemical Engineering Journal, 2024)

A novel process for efficient utilization of bamboo fiber resource in dissolving pulp production by fiber fractionation: Laboratory study and mill trials - Yishan Liu; Chenglong Fu; Lianli Liu; Ke Wang; Ting Wu; Jingjing Wu; Junmiao Zhang; Zhanghong Xie; Yinchuan Xu; Chao Duan; Yonghao Ni; Zhibin He (Bioresource Technology, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Degradation of pharmaceuticals in UV/H2O2 process: EEM-based kinetic model, transformation products and corresponding toxicity evaluation - Shaoting Lei; LinChang Guan; Fu Liu; Qingmiao Yu; Ke Xu; Hongqiang Ren; Jinju Geng (Journal of Environmental Chemical Engineering, 2024)

Molar ratio of (-)-epicatechin and (-)-epigallocatechin gallate determined their enzymatic oxidation products and color characteristics - Li Lian; Yuqing Cui; Mingchun Wen; Daniel Granato; Yong-Quan Xu; Yan-Qing Fu; Zongde Jiang; Jiaping Ke; Xiaochun Wan; Liang Zhang (Food Bioscience, 2024)

Soil health assessment under different soil and irrigation types in the agro-pastoral ecotone of northern China - Huayu Lu; Xiangyang Chen; Ke Ma; Shiwei Zhou; Jiali Yi; Yunjiao Qi; Jiale Hao; Fu Chen; Xinya Wen (CATENA, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Dynamics of tannin variations in mangrove leaf litter decomposition and their effects on environmental nitrogen and microbial activity - Tao Lang; Xinran Ke; Jian Wei; Muzammil Hussain; Mingdang Li; Changjun Gao; Mingguo Jiang; Yibing Wang; Yijian Fu; Kunhua Wu; Wenyan Zhang; Nora Fung-yee Tam; et al. (Science of The Total Environment, 2024)

Concentration identification and endpoint-oriented health risk assessments on a broad-spectrum of organic compounds in atmospheric fine particles: A sampling experimental study in Beijing, China - Ke Gao; Linxiao Wang; Yifan Xu; Yidan Zhang; Haonan Li; Jie Fu; Jianjie Fu; Liping Lu; Xinghua Qiu; Tong Zhu (Science of The Total Environment, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Surimi freshness monitoring of 4D printing material with anthocyanin - Jun-qi Zhan; Jing-jing Fu; Dan-li Jin; Yan-wei Yuan; Shi-ke Shen; Gao-shang Li; Yue-wen Chen (Journal of Food Engineering, 2023)

Combination of radio frequency heating and antibacterial agents for microorganism control in the production of packaged tofu - Baozhong Cui; Ke Wang; Nan Hu; Yanan Sun; Chao Mao; Pengfei Ye; Huiyun Pang; Yequn Wang; Hongfei Fu; Xiangwei Chen; Yunyang Wang (Food Control, 2023)

Rapid and noninvasive cell assay by microfluidic-integrated intracavity evanescent field absorption in a fiber ring laser - Jia Shi; Ziyi Xu; Ke Yang; Xianguo Li; Cuijuan Guo; Hua Bai; Weiling Fu; Pingjuan Niu; Jianquan Yao; Xiang Yang (Analytica Chimica Acta, 2023)

Mitigating greenhouse gas emissions from agriculture in Benin: spatial estimation and reduction options - Iskid Jacquet; Jianjun Zhang; Ke Wang; Sen Liang; Shu Fu; Shidong Liu (Environment, Development and Sustainability, 2023)

Observations on the embryonic development of the mud crab, Scylla paramamosain - Li-Kun Xu; Ke-Yi Ma; Feng-Ying Zhang; Wei Wang; Ling-Bo Ma; Zhong-Wen Jin; Ming Zhao; Wei Chen; Yin Fu; Chun-Yan Ma; Zhi-Qiang Liu (Frontiers in Marine Science, 2023)
To investigate the embryonic development of the mud crab Scylla paramamosain , we analyzed three critical parameters: egg color of, embryo morphology (through conventional and laser scanning confocal microscopy), and the distribution of cell divisions. During embryonic development, the egg color exhibited a progressive transition, shifting from orange to reddish-orange, then to brown, before ultimately darkening to black. Each embryo displayed a spherical shape, measuring approximately 280 μm in diameter, characterized by a smooth surface devoid of any depressions. The embryonic cell division was in the form of mixed oogenesis, comprised of complete division in the early stage, spiral oogenesis in the middle stage and surface division in the late stage. It is noteworthy that the blastopore appeared at the position where the transparent area and cell aggregation just appeared under the microscope, and the blastomere was a characteristic of the embryo entering the gastrulation stage. After entering the gastrulation stage, the cells aggregated towards the blastopore and formed two symmetrical cell clusters, which formed a V-shape with the void of the classic blastopore. When the transparent region occupied approximately 1/5 of the embryo ’ s volume, the embryo entered the nauplius stage, and the thoracic and abdominal armor, as well as the optic lobe and abdominal limb primordia, could be clearly distinguished. The appearance of the compound eye pigment band indicated the stage of compound eye pigment formation. At this time, the transparent area accounted for 1/4 of the embryo and a large number of ganglia appeared. The change of the compound eye pigment band from red to black was also one of the reasons for the blackening of the egg color of the crabs. The data obtained through this study have potential applications in the determination of embryonic development status and obtaining of high-quality seeds for S. paramamosain culture.

Deriving fine-scale patterns of sea surface temperature in coral reef habitats using the Landsat 8 thermal infrared sensor - Xiu-Ling Zuo; Ke-Fu Yu; Bin-Ni Qin; Xiao-Peng Duan; Zuo-Fang Yao; Fen-Zhen Su (Frontiers in Marine Science, 2023)
The available sea surface temperature (SST) products are too coarse to assess the fine-scale (<1 km) SST variations related to coral bleaching. In this study, we proposed an optimal SST inversion model using Landsat 8 thermal infrared sensor (TIRS) images to derive fine-scale SST patterns in the coral reef habitats of the Xisha Islands, South China Sea. Our study included two parts: 1) six SST inversion models were developed using the radiative transfer method and the split window (SW) algorithm in the hot season and cool season, from which the optimal SST inversion model was determined; and 2) the optimal model was applied to 47 Landsat 8 TIRS images to derive the SST spatial and temporal pattern among the geomorphic zones of six reefs in hot and cool season conditions. Compared with the measured sea temperature data and the verified MODIS SST products, the SST6 model using the SW algorithm was optimal, with an RMSE of approximately 0.64°C in the hot season. The average SST results usually had a pattern of reef flat > lagoon > reef slope/offshore sea. The reef flat was usually approximately 0.05°C–0.2°C hotter than the lagoon in the hot season. The SST in the lagoon also increased from south to north and the shallow lagoon was usually warmer than the deep lagoon in the hot season. Our results suggested that scleractinian corals in the reef flat and the lagoon were more susceptible to bleaching-level thermal stress than other geomorphic zones. During the cool season, the SST fluctuated markedly among coral reefs and geomorphic zones.

Topsoil selenium (Se) under Se-rich farming in China: Current status, cropping impacts and ecological risk assessment - Li Qian; Ting Wang; Yajuan Shi; Qiuyun Xu; Xuan Zhou; Lingjie Ke; Ruoyu Liang; Chuancheng Fu; Xiaoqi Zheng; Guoxin Sun (Journal of Environmental Management, 2023)

Class 1 integron carrying qacEΔ1 gene confers resistance to disinfectant and antibiotics in Salmonella - Shujuan Chen; Jingxia Fu; Ke Zhao; Shengzhi Yang; Chun Li; Petri Penttinen; Xiaolin Ao; Aiping Liu; Kaidi Hu; Jianlong Li; Yong Yang; Shuliang Liu; et al. (International Journal of Food Microbiology, 2023)

High internal phase Pickering emulsions stabilized by modified sturgeon myofibrillar protein for quercetin delivery - Shi-ke Shen; Yue-wen Chen; Wen-tao Yu; Qian-yun Bu; Jing-jing Fu; Zi-yi Pan; Yi-tong Wang (Food Hydrocolloids, 2023)

Salt tide affecting algae-laden micropolluted surface water treatment and membrane performance based on BDD electro-oxidation coupled with ceramic membrane process - Xing Du; Bingxuan Li; Zhongjian Zhuang; Ke Kuang; Wei Song; Dachao Lin; Caixia Fu; Zhihong Wang (Environmental Research, 2023)

Prussian blue analogues-derived zero valent iron to efficiently activate peroxymonosulfate for phenol degradation triggered via reactive oxygen species and high-valent iron-oxo complexes - Tong Wei; Xin-Sheng Zhu; Qi-Xue Wang; Ke-Ke Xu; Fu-Kai Tang; Ming-Zhu Zhang; Shi-Wen Lv; Feng Ge (Environmental Research, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Magmatic fluids responsible for lode gold mineralization in the giant Linglong deposit at Jiaodong, North China Craton: Constraints from LiO isotopes - Shao-Rui Zhao; Zhan-Ke Li; Zu-Wei Lin; Jian-Feng Gao; Hua-Shan Sun; Martin Yan Hei Li; Xin-Fu Zhao (Chemical Geology, 2023)

Detecting the magical yellow-blue demarcation off the Yellow River Estuary from the space - Peng Li; Shenliang Chen; Hongyu Ji; Yaoshen Fan; Yutao Fu; Baichuan Ran; Yinghai Ke (Frontiers in Marine Science, 2023)
River deltas rank among the most ecologically and socio-economically valuable environments on the planet. The Yellow River Delta in China is not only home to young wetland ecosystem, but also to world-renowned tourism resources. One of these was the unique yellow-blue demarcation line (YBDL), formed in the Yellow River Estuary (YRE) as a result of the meeting of terrestrial sediment-laden river water and clear sea water, which had developed into a famous attraction and generated significant tourism revenues. Moreover, its distribution was of vital ecological and geomorphological importance due to association with the dynamics of estuarine turbidity plume. However, little is yet known about the dynamics and influencing factors of YBDL. In this study, we proposed an integrated method for extracting YBDL from satellite imagery and investigated the spatiotemporal distributions of YBDL during the flood season (June-October) from 2016 to 2022 using multi-source satellite imageries. The average relative error of our algorithm reached 10.53%. The results indicated that the YBDL started to frequently occur after 2018, mainly distributed within 10 km off the YRE, with two types of short straight and long curved shapes. July was the period with the highest frequency and most widespread distribution of YBDL. The riverine water and sediment discharge controlled 45.9% of the variations in YBDL length, and the extreme flooding, as well as the implementation of Water-Sediment Regulation Scheme, significantly increased the distribution extent of the YBDL. The morphology of river distributary mouths dominated the changes in the YBDL distribution centres, and the north distributary mouth experienced dramatic evolution in the last three years, with an increased YBDL distribution. Tidal currents could promote the development of YBDL at the front of the river mouth plumes while inhibiting the YBDL on the other side. This study is the first systematic investigation of the spatiotemporal evolutions and driving mechanisms of YBDL in the YRE, which could provide a reference for tourism planning and YRE National Park construction.

Urinary essential and toxic metal mixtures, and type 2 diabetes mellitus: Telomere shortening as an intermediary factor? - Duo Zhang; Xiao Chen; Ke Huang; Quanzhi Zheng; Ying Fu; Jiaojiao Ma; Xiaohu Ren; Benhong Xu; Peiyi Liu; Jianjun Liu; Shaoyou Lu (Journal of Hazardous Materials, 2023)

L-type lectin receptor-like kinase OsCORK1 as an important negative regulator confers copper stress tolerance in rice - Ke Wang; Shen Li; Zhaoyan Yang; Cong Chen; Yihan Fu; Haitao Du; Hongzheng Sun; Junzhou Li; Quanzhi Zhao; Changqing Du (Journal of Hazardous Materials, 2023)

Impact of COVID-19 pandemic on profiles of antibiotic-resistant genes and bacteria in hospital wastewater - Liang Zhao; Ziquan Lv; Liangqiang Lin; Xiaowei Li; Jian Xu; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Pollution, 2023)

Two-point-one-line modularized strategy combined with Holliday-junction button probes for multiloci SNPs long-range distribution analysis - Wang Luo; You Wu; Xueping Chen; Li Zhang; Li Wang; Dan Bai; Qian Liu; Ting Wang; Hongyan Yu; Yaxing Xie; Yixin Fu; Zhongzhong Wang; et al. (Chemical Engineering Journal, 2023)

Solution plasma-assisted synthesis of oxyhydroxides for advanced electrocatalytic water splitting - Wentao Bao; Ke Lu; Pengjie Fu; Jinfeng Yang; Ying Tang; Yaxin Sun; Zhen Yang; Fuxi Bao; Zongyuan Wang; Xiaodong Yang; Feng Yu (Chemical Engineering Journal, 2023)

Risk-based irrigation decision-making for the Shihmen Reservoir Irrigation District of Taiwan - Sheng-Fu Tsai; Dong-Hong Wu; Gwo-Hsing Yu; Ke-Sheng Cheng (Paddy and Water Environment, 2023)

Vegetation structural shift tells environmental changes on the Tibetan Plateau over 40 years - Yanfen Wang; Kai Xue; Ronghai Hu; Boyang Ding; Hong Zeng; Ruijin Li; Bin Xu; Zhe Pang; Xiaoning Song; Congjia Li; Jianqing Du; Xiuchun Yang; et al. (Science Bulletin, 2023)

Revolutionizing wound healing: Ultrashort pulse electric fields in seconds for highly aligned extracellular matrix and efficient cell migration - Xiao-Wei Xiang; Hao-Tian Liu; Wei Liu; Ze-Yao Yan; Yu-Lian Zeng; Ya-Jun Wang; Jing Liu; Yu-Chen Chen; Sai-Xi Yu; Cai-Hui Zhu; Xiao-Nan Tao; Chen Wang; et al. (Chemical Engineering Journal, 2023)

Characterization and genome analysis of Acinetobacter oleivorans S4 as an efficient hydrocarbon-degrading and plant-growth-promoting rhizobacterium - Panpan Wang; Haiying Wei; Tan Ke; Yaojia Fu; Yuyang Zeng; Chaoqi Chen; Lanzhou Chen (Chemosphere, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Sulfur isotopic evidence for global marine anoxia and low seawater sulfate concentration during the Late Triassic - Wei Tang; Jian Wang; Hengye Wei; Xiugen Fu; Puyang Ke (Journal of Asian Earth Sciences, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Study on Ultimate Strength and Dip Effect of Coal Pillar in Steeply Dipping Coal Seam - Qiang Fu; Ke Yang; Zhen Wei; Xiang He (Geotechnical and Geological Engineering, 2023)

Strong photo-thermal coupling effect boosts CO2 reduction into CH4 in a concentrated solar reactor - Lei Xu; Yuqi Ren; Yiwei Fu; Maochang Liu; Fengfan Zhu; Miao Cheng; Jiancheng Zhou; Wenshuai Chen; Ke Wang; Nan Wang; Naixu Li (Chemical Engineering Journal, 2023)

Near unity broadband emissivity and ultralow thermal conductivity from yttrium niobate-based ceramics - Guoliang Chen; Benzhi Min; Haoyang Fu; Siqi Ma; Ke Li; Shuqi Wang; Yaming Wang; Jianyun Cao; Jun Qiu; Yong Shuai; Shuzhou Li; Yongchun Zou; et al. (Chemical Engineering Journal, 2023)

Designing Er3+ Single-doped ternary sulfide for highly efficient upconversion luminescence under 1550 nm excitation - Hong Wang; Zhe He; Ke Cai; Limin Wei; Yang Xu; Yao Fu; Mingming Xing; Ying Tian (Chemical Engineering Journal, 2023)

Biomimetic optimized concept with Murray networks for accelerated solar-driven water evaporation - Ruofei Zhu; Ke Li; Dan Wang; Jipeng Fei; Jun Yan Tan; Shuzhou Li; Jichao Zhang; Hong Li; Shaohai Fu (Chemical Engineering Journal, 2023)

Optimizing rice in-season nitrogen topdressing by coupling experimental and modeling data with machine learning algorithms - Jiayi Zhang; Zhaopeng Fu; Ke Zhang; Jiayu Li; Qiang Cao; Yongchao Tian; Yan Zhu; Weixing Cao; Xiaojun Liu (Computers and Electronics in Agriculture, 2023)

High-efficiency promotion on dechlorination of polyvinyl chloride in subcritical water treatment by introducing waste concrete - Fu-Rong Xiu; Ruiqi Yang; Yingying Qi; Ke Zhou; Jiali Wang; Wenting Shao; Haipeng Zhou; Longsheng Zhan (Process Safety and Environmental Protection, 2023)

Rejuvenation effect of aged SBS-modified asphalt utilizing molecule analysis - Ke Shi; Feng Ma; Jenny Liu; Zhen Fu; Ruimeng Song; Dongdong Yuan; Chen Li (Journal of Cleaner Production, 2023)

Leaky Gut Plays a Critical Role in the Pathophysiology of Autism in Mice by Activating the Lipopolysaccharide-Mediated Toll-Like Receptor 4–Myeloid Differentiation Factor 88–Nuclear Factor Kappa B Signaling Pathway - Fang Li; Haoran Ke; Siqi Wang; Wei Mao; Cexiong Fu; Xi Chen; Qingqing Fu; Xiaori Qin; Yonghua Huang; Bidan Li; Shibing Li; Jingying Xing; et al. (Neuroscience Bulletin, 2023)
Increased intestinal barrier permeability, leaky gut, has been reported in patients with autism. However, its contribution to the development of autism has not been determined. We selected dextran sulfate sodium (DSS) to disrupt and metformin to repair the intestinal barrier in BTBR T + tf/J autistic mice to test this hypothesis. DSS treatment resulted in a decreased affinity for social proximity; however, autistic behaviors in mice were improved after the administration of metformin. We found an increased affinity for social proximity/social memory and decreased repetitive and anxiety-related behaviors. The concentration of lipopolysaccharides in blood decreased after the administration of metformin. The expression levels of the key molecules in the toll-like receptor 4 (TLR4)–myeloid differentiation factor 88 (MyD88)–nuclear factor kappa B (NF-κB) pathway and their downstream inflammatory cytokines in the cerebral cortex were both repressed. Thus, “leaky gut” could be a trigger for the development of autism via activation of the lipopolysaccharide-mediated TLR4–MyD88–NF-κB pathway.

Fluid evolution and ore genesis of the A'gui Cu deposit in southern Great Xing'an Range, Northeast China: Evidence from fluid inclusion and C–H–O–S–Pb isotopes - Xue Wang; Ke-yong Wang; Li-juan Fu; Qing-ying Zhao; Qing-fei Sun; Chao Zhang (Geochemistry, 2023)

Physicochemical and functional properties of chitosan-based edible film incorporated with Sargassum pallidum polysaccharide nanoparticles - Ke Zhang; Qing Chen; Jie Xiao; Lijun You; Siming Zhu; Chao Li; Xiong Fu (Food Hydrocolloids, 2023)

Microbial species from multiple maternal body sites shape the developing giant panda ( Ailuropoda melanoleuca ) cub gut microbiome - Wei Guo; Ke Ren; Ruihong Ning; Caiwu Li; Yu Zhang; Yunong Gan; Xiaoyan Fu; Cenjun Xiao; Yaoyu Pang; Lei Cheng; Siyuan Zhang; Desheng Li; et al. (Molecular Ecology, 2023)
The gut microbiome of the giant panda ( Ailuropoda melanoleuca ) plays a vital role in nutrient acquisition from its specialized bamboo diet. Giant panda cubs harbour significantly different gut microbiota during their growth and development when feeding on milk before switching to bamboo. The fetal gut is sterile, and following birth, mother‐to‐infant microbial transmission has been implicated as a seeding source for the infant gut microbiota. Details of this transmission in giant pandas remain unclear. In this study, faecal samples were collected from seven panda mother–cub pairs when the cubs were 4–16 months old. Additional samples from the cubs' diet, soil and drinking water, and multiple body sites of the mothers were collected. Bacterial 16S rRNA gene sequencing and shotgun metagenomic sequencing were performed to determine the source and potential transmission routes of the cub gut microbiome. Source tracking analysis showed that maternal vagina, milk and faeces were the primary contributory sources of microbes, shaping the cub gut microbiome. Bacterial species from maternal faeces persisted the longest in the cub gut. Bacterial species in the diet contributed to the microbial community. Metagenomics analysis indicated that the predicted metabolic pathways of the gut microbiome also varied at different growth stages. Gut colonization with bacteria from various body sites of the mothers provides a foundational microbial community that is beneficial in fulfilling the evolving dietary needs of the cubs. This study suggests that mother‐to‐cub transmission is indispensable in shaping the gut microbiome of the developing panda cub.

Effect of combined aging treatment on biochar adsorption and speciation distribution for Cd(II) - Yuxin Ke; Fuxiang Zhang; Zulin Zhang; Rupert Hough; Qiang Fu; Yi-Fan Li; Song Cui (Science of The Total Environment, 2023)

A broadly neutralizing nanobody targeting the highly conserved S2 subunit of sarbecoviruses - Xiaoyun Wang; Yufeng Xie; Honghui Liu; Wenwen Lei; Ke Xu; Lili Wu; Ruiwen Fan; Guizhen Wu; George Fu Gao; Qihui Wang (Science Bulletin, 2023)

The mobility and fate of Cr during aging of ferrihydrite and ferrihydrite organominerals - Yao Zhao; Alba Otero-Fariña; Ke-Qing Xiao; Oliver W. Moore; Steven A. Banwart; Fu-Jun Ma; Qing-Bao Gu; Caroline L. Peacock (Geochimica et Cosmochimica Acta, 2023)

Molecular insights into enhanced nitrogen removal induced by trace fluoroquinolone antibiotics in an anammox system - Xuejiao Qiao; Chenkun Fu; Yizhen Chen; Fang Fang; Yaoyu Zhang; Lingyun Ding; Kai Yang; Baozhu Pan; Nan Xu; Ke Yu; Huchun Tao; Lijuan Zhang (Bioresource Technology, 2023)

Production and Biological Effects of Extracellular Vesicles from Adipose-Derived Stem Cells Were Markedly Increased by Low-Intensity Ultrasound Stimulation for Promoting Diabetic Wound Healing - Yi Zheng; Peng Xu; Chuqiao Pan; Yikai Wang; Zibo Liu; Yahong Chen; Chuhsin Chen; Shibo Fu; Ke Xue; Qimin Zhou; Kai Liu (Stem Cell Reviews and Reports, 2023)

Strategies for improving the photocatalytic performance of metal-organic frameworks for CO2 reduction: A review - Ke Guo; Ijaz Hussain; Guang′an Jie; Yanghe Fu; Fumin Zhang; Weidong Zhu (Journal of Environmental Sciences, 2023)

Sourdough yeast-bacteria interactions results in reduced immunogenicity by increasing depolymerization and hydrolysis of gluten - Wenhui Fu; Xin Jia; Chenglong Liu; Xiao Meng; Ke Zhang; Sha Tao; Wentong Xue (Innovative Food Science & Emerging Technologies, 2023)

FAS-mediated circRNA-miRNA-mRNA Crosstalk Network Regulates Immune Cell Infiltration in Cerebral Infarction - Ke Ying; Juan Chen; Zhenhui Fu; Bo Ren (Journal of Molecular Neuroscience, 2023)

The MocR family transcriptional regulator DnfR has multiple binding sites and regulates Dirammox gene transcription in Alcaligenes faecalis JQ135 - Si‐Qiong Xu; Xiao Wang; Lu Xu; Ke‐Xin Wang; Yin‐Hu Jiang; Fu‐Yin Zhang; Qing Hong; Jian He; Shuang‐Jiang Liu; Ji‐Guo Qiu (Environmental Microbiology, 2023)
Microbial ammonia oxidation is vital to the nitrogen cycle. A biological process, called Dirammox ( dir ect amm onia ox idation, NH 3 →NH 2 OH→N 2 ), has been recently identified in Alcaligenes ammonioxydans and Alcaligenes faecalis . However, its transcriptional regulatory mechanism has not yet been fully elucidated. The present study characterized a new MocR‐like transcription factor DnfR that is involved in the Dirammox process in A. faecalis strain JQ135. The entire dnf cluster was composed of 10 genes and transcribed as five transcriptional units, that is, dnfIH , dnfR , dnfG , dnfABCDE and dnfF . DnfR activates the transcription of dnfIH , dnfG and dnfABCDE genes, and represses its own transcription. The intact 1506‐bp dnfR gene was required for activation of Dirammox. Electrophoretic mobility shift assays and DNase I footprinting analyses showed that DnfR has one binding site in the dnfH ‐ dnfR intergenic region and two binding sites in the dnfG ‐ dnfA intergenic region. Three binding sites of DnfR shared a 6‐bp repeated conserved sequence 5′‐GGTCTG‐N 17 ‐GGTCTG‐3′ which was essential for the transcription of downstream target genes. Cysteine and glutamate act as possible effectors of DnfR to activate the transcription of transcriptional units of dnfG and dnfABCDE , respectively. This study provided new insights in the transcriptional regulation mechanism of Dirammox by DnfR in A. faecalis JQ135.

Association of blood mercury levels with bone mineral density in adolescents aged 12–19 - Ke Xu; Bingqian Gao; Tingfeng Liu; Jiayi Li; Yixin Xiang; Yicheng Fu; Mingyi Zhao (Environmental Science and Pollution Research, 2023)

Linking trait network to growth performance of submerged macrophytes in response to ammonium pulse - Guixiang Yuan; Xiaoyao Tan; Peiqin Guo; Ke Xing; Zhenglong Chen; Dongbo Li; Sizhe Yu; Hui Peng; Wei Li; Hui Fu; Erik Jeppesen (Water Research, 2023)

Two new terpenoids and other constituents from Salvia cavaleriei and their antibacterial activities - Yu-Min Zhao; Ke Li; Han-Fei Liu; Jin-Yu Li; Jian Fu; Hua-Yong Lou; Wei-Dong Pan (Phytochemistry Letters, 2023)

Visible light-regulated thermal catalytic selectivity induced by nonthermal effects over CuNi/CeO2 - Xuanyu Yue; Ke Wang; Zhou Yang; Wenkang Ni; Zizhong Zhang; Wenxin Dai; Xianzhi Fu (Chemical Engineering Journal, 2023)

“One stone, five birds”: Ultrabright and multifaceted carbon dots for precise cell imaging and glutathione detection - Zihao Wang; Ke-Fei Xu; Gang Wang; Samran Durrani; Fengming Lin; Fu-Gen Wu (Chemical Engineering Journal, 2023)

Developing a prediction model for segment joint opening in an underwater shield tunnel - Jin-Quan Liu; Ka-Veng Yuen; Jin-Fu Ke; Wei-Zhong Chen (Marine Georesources & Geotechnology, 2023)

Optimizing crop rotation increases soil carbon and reduces GHG emissions without sacrificing yields - Yuhao Yang; Jinsong Ti; Jun Zou; Yao Wu; Robert M. Rees; Matthew Tom Harrison; Wenxin Li; Wenhai Huang; Suya Hu; Ke Liu; Xinya Wen; Fu Chen; et al. (Agriculture, Ecosystems & Environment, 2023)

Paracoccus marinaquae sp. nov., isolated from coastal water of the Yellow Sea - Hua-Peng Xue; Zi-Yue Fu; Wei He; Lei Wang; Wen-Jun Li; Ai Hua Zhang; Jian-Ke Huang; Dao-Feng Zhang; Zhe Zhao (Archives of Microbiology, 2023)

Occurrence and risk assessment of antibiotics in feces of elderly individuals in Shenzhen - Yuan Zhang; Ziquan Lv; Xiaowei Li; Kunxia Zhao; Suli Huang; Yuhua Chen; Yulin Fu; Changfeng Peng; Tingting Cao; Yuebin Ke; Xi Xia (Environmental Science and Pollution Research, 2023)

Pathology, Enzyme Activity and Immune Responses after Cryptocaryon irritans Infection of Golden Pompano Trachinotus ovatus (Linnaeus 1758) - Hua-Yang Guo; Wen-Fu Li; Ke-Cheng Zhu; Bao-Suo Liu; Nan Zhang; Bo Liu; Jing-Wen Yang; Dian-Chang Zhang (Journal of Marine Science and Engineering, 2023)
Golden pompano (Trachinotus ovatus) has become an economically important fish in China in the past decade. However, Cryptocaryon irritans, a parasitic ciliate, causes considerable economic losses in the mariculture of T. ovatus. To characterize the pathogenesis of C. irritans in T. ovatus, the pathological properties, immune-related enzyme activity and expression of the NEMO gene was analysed. The results from the histological sections showed that there was considerable metamorphosis and hyperplasia in the parasitized sites (skin) with leukocyte aggregation and mucous cell increases after C. irritans infection. Moreover, the activities of four enzymes, that is, alkaline phosphatase (AKP), acid phosphatase (ACP), superoxide dismutase (SOD) and lysozyme (LZM), were significantly increased in different tissues after C. irritans infection. Furthermore, the ORF of T. ovatus NF-kappa-B essential modulator (ToNEMO) measures 1650 bp, encoding 548 amino acids. The ToNEMO transcripts were universally expressed in all examined tissues, with higher levels being observed in the immune-relevant and central nervous tissues. The mRNA levels of ToNEMO after C. irritans infection were significantly increased in the gill, skin, liver, spleen and head kidney. These results suggested that ToNEMO might be involved in immune responses and helped to elucidate the physiological response after the C. irritans infection of fish.

Within-species plant phylogeny drives ectomycorrhizal fungal community composition in tree roots along a timberline - Teng Yang; Luyao Song; Han-Yang Lin; Ke Dong; Xiao Fu; Gui-Feng Gao; Jonathan M. Adams; Haiyan Chu (Soil Biology and Biochemistry, 2023)

Dynamics of heavy metals during the development and decomposition of leaves of Avicennia marina and Kandelia obovata in a subtropical mangrove swamp - Tao Lang; Nora Fung-yee Tam; Muzammil Hussain; Xinran Ke; Jian Wei; Yijian Fu; Mingdang Li; Xiazi Huang; Shuyan Huang; Zhangjing Xiong; Kunhua Wu; Fenglan Li; et al. (Science of The Total Environment, 2023)

Stepwise northward compression in the northeastern Tibetan Plateau: Insights from the chronology of the Baima Basin - Hao Liang; Ke Zhang; Jianli Fu; Weitao Wang; Peizhen Zhang; Rodney Grapes; Zhanwu Ma; Yipeng Zhang; Zhigang Li; Yonggang Yan; Gege Hui; Chuang Sun; et al. (Global and Planetary Change, 2023)

Streptomyces Spinosirectus sp. nov., Isolated From the Medicinal Plant Xanthium Sibiricum - Yin-Feng Wang; Si-Ren Hu; Li Fu; Yan Xiao; Xin-Ke Tang; Jian Gao (Current Microbiology, 2023)

The self-powered electrochemical biosensing platform with multi-amplification strategy for ultrasensitive detection of microRNA-155 - Yong-ping Gao; Ke-jing Huang; Fu-ting Wang; Yang-yang Hou; Lu-di Zhao; Bo-ya Wang; Jing Xu; Honglei Shuai; Guoqiang Li (Analytica Chimica Acta, 2023)

Optimizing nitrogen application and sowing date can improve environmental sustainability and economic benefit in wheat-rice rotation - Zhaopeng Fu; Ke Zhang; Jiayi Zhang; Yu Zhang; Qiang Cao; Yongchao Tian; Yan Zhu; Weixing Cao; Xiaojun Liu (Agricultural Systems, 2023)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

Transcriptome-Based Analysis of the Response Mechanism of Leopard Coralgrouper Liver at Different Flow Velocities - Min Yang; Jin Gao; Hongji Ke; Yongbo Wang; Jinye Liu; Xin Wen; Shuyuan Fu; Jiang Wang (Fishes, 2022)
The velocity of water can cause differences in the growth of inhabitant fish, thereby functioning as an important aquatic environmental factor. In order to explore the response mechanism of Leopard Coralgrouper (Plectropomus leopardus) under different flow velocities, P. leopardus fish of the same sizes were fed in water characterized by three different flow rates (5 cm/s, 10 cm/s, and 20 cm/s) for 150 d, after which the differences in growth and the levels of liver oxidative stress kinase were analyzed. Additionally, potential underlying regulatory pathways were explored using comparative transcriptomic approaches. The results showed that in the feeding environment involving a flow rate of 10 cm/s, the weight increase of P. leopardus and its liver contents of glutathione peroxidase (GPX), alanine aminotransferase (ALT), and superoxide dismutase (T-SOD) were significantly higher than for the other two groups. After matching the comparative transcriptomic results between group pairs (5 cm/s and 10 cm/s, 5 cm/s and 20 cm/s, and 10 cm/s and 20 cm/s), a total of 225 common differential gene expressions were screened. The KEGG pathway enrichment analysis showed that these genes were mainly involved in protein processing in the endoplasmic reticulum, the TGF-β signaling pathway, fatty acid metabolism, fatty acid synthesis, and other pathways. These results not only provide a theoretical basis for the selection of flow velocity in the culture environment of P. leopardus, but also reveal its potential means of adaption to different flow velocities.

iTRAQ-based proteomics analysis of diethylstilbestrol induced dysfunction of testicular gubernaculum development in mouse - Hongyan Ping; Degang Wang; Maxian Fu; Kaihong Chen; Jiuhong Zhang; Ke Li; Xuewu Jiang; Shouxing Duan; Xuan Zhang (Molecular & Cellular Toxicology, 2022)

Quantifying the associations of the air pollutant SO2 on outpatient visits for conjunctivitis in Hangzhou, China - Zhijian Chen; Qiuli Fu; Lizhi Wu; Peiwei Xu; Dandan Xu; Xuejiao Pan; Xiaoming Lou; Xiaofeng Wang; Ke Yao; Zhe Mo (Environmental Science and Pollution Research, 2022)

Stat5−/− CD4+ T cells elicit anti-melanoma effect by CD4+ T cell remolding and Notch1 activation - Ke Jin; Tong Li; Zhiyong Miao; Jingjing Ran; Luyu Chen; Dachao Mou; Chuang Wang; Shasha Wu; Hanshuo Yang; Xin-Yuan Fu (Science China Life Sciences, 2022)

The traditional uses, secondary metabolites, and pharmacology of Eleutherococcus species - Yue-Hui Huang; Jin-Tao Li; Ke Zan; Jun Wang; Qiang Fu (Phytochemistry Reviews, 2022)

miR-517b-3p promotes the progression of portal vein tumor thrombus via activating Wnt/β-catenin signaling pathway in hepatocellular carcinoma - Rui-Sheng Ke; Kun-Zhai Huang; De-sheng Bao; Jing-Rui Yang; Hua-xiang Wang; Li-Zhi Lv; Yi Jiang; Zhao-Hui Liu; Fu-Xing Zhang (Molecular Biology Reports, 2022)

Reliable reference genes for qPCR normalization in females of the mirid predator, Cyrtorhinus lividipennis (Hemiptera: Miridae) - Kui Hu; Ke Chen; Baobao Fu; Jianqi Liu; Yan Li; Qinjian Pan; Fang Liu (Biologia, 2022)

Diminished miR-374c-5p negatively regulates IL (interleukin)-6 in unexplained recurrent spontaneous abortion - Lin Zhao; Li Han; Guozhen Hei; Ran Wei; Zhen Zhang; Xiaoxiao Zhu; Qiang Guo; Chu Chu; Xiaoxiao Fu; Ke Xu; Xia Li (Journal of Molecular Medicine, 2022)

Does high-speed rail improve China’s urban environmental efficiency? Empirical evidence from a quasi-natural experiment - Ke-Liang Wang; Su-Qin Pang; Fu-Qin Zhang; Zhuang Miao (Environmental Science and Pollution Research, 2022)

Assessing the impacts of natural disasters on rice production in Jiangxi, China - Xiao Fu; Guannan Zhao; Weicheng Wu; Bin Xu; Jie Li; Xiaoting Zhou; Xinxin Ke; Yuan Li; Wenjing Li; Cuimin Zhou; Jingheng Jiang; Ming Zhang; et al. (International Journal of Remote Sensing, 2022)

Functional characterization of tyrosine decarboxylase genes that contribute to acteoside biosynthesis in Rehmannia glutinosa - Yan Hui Yang; Mu Rong Yang; Jian Yu Zhu; Ke Wei Dong; Yan Jie Yi; Rui Fang Li; Lei Zeng; Chang Fu Zhang (Planta, 2022)

The effect of preoperative statin treatment on acute kidney injury in elderly patients undergoing valve replacement surgery - Bing-qi Fu; Xue-biao Wei; Zedazhong Su; Ying-wen Lin; Zu-hui Ke; Tong Tan; Ji-yan Chen; Shou-hong Wang; Dan-qing Yu (European Journal of Clinical Pharmacology, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

miR-181b-5p Promotes the Progression of Cholangiocarcinoma by Targeting PARK2 via PTEN/PI3K/AKT Signaling Pathway - Zhe-Long Jiang; Fu-Xing Zhang; Hong-Liang Zhan; He-Jun Yang; Si-Yu Zhang; Zhao-Hui Liu; Yi Jiang; Li-Zhi Lv; Rui-Sheng Ke (Biochemical Genetics, 2022)

Characteristics of fine particulate matter (PM2.5) at Jinsha Site Museum, Chengdu, China - Jialin Deng; Luman Jiang; Wenwen Miao; Junke Zhang; Guiming Dong; Ke Liu; Juncheng Chen; Tong Peng; Yao Fu; Yunpei Zhou; Xue Huang; Mengqian Hu; et al. (Environmental Science and Pollution Research, 2022)

Infestation and distribution of mites on the Yunnan red-backed vole (Eothenomys miletus) in Yunnan Province of southwest China between 2001 and 2015 - Rong Xiang; Xian-Guo Guo; Tian-Guang Ren; Cheng-Fu Zhao; Rong Fan; Zhi-Wei Zhang; Ke-Yu Mao; Pei-Ying Peng; Xiao-Bin Huang; Ti-Jun Qian (Biologia, 2022)

Identification of bacterial blight resistance genes in rice landraces from Yunnan Province, China - Caimei Zhao; Fuyou Yin; Ling Chen; Dingqin Li; Suqin Xiao; Qiaofang Zhong; Bo Wang; Xue Ke; Jian Fu; Xiang Li; Yue Chen; Lingxian Wang; et al. (Australasian Plant Pathology, 2022)
Bacterial blight (BB), a serious bacterial disease caused by pathogen Xanthomonas oryzae pv. oryzae ( Xoo ) affects rice growth and yield. Yunnan Province is regarded as a center of rice diversity in China and indeed the world, and has abundant rice landrace resources, which may offer prospective candidate donors in rice improvement and breeding. In this study, a set of 200 rice landraces were evaluated to determine their resistance to 10 pathogenic Xoo strains resistance by the leaf-clipping method. The results indicated that the tested rice landraces had different resistance levels against different Xoo strains. Multiple comparisons showed that the Xoo strain PXO99 was virulent to the tested rice landraces. Sixty-six rice landraces conferred resistance against at least one Xoo strain. These resistant rice landraces screened were then performed the presence of 14 cloned BB resistance genes by closely linked molecular markers and designed specific primers. The results showed that none of these resistant accessions contained xa13 , Xa21 , Xa27 , and Xa45(t) homologous fragments, while 9, 24, 4, 7, 9, 15, 1, 5, 4 and 27 accessions contained Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa7 , Xa10 , Xa23 and xa25 homologous fragments, respectively. Sequence analysis further revealed that nucleotide variations around functional nucleotide polymorphisms region were observed within these accessions containing the Xa1 , Xa2/Xa31(t) , Xa14 , Xa3/Xa26 , Xa4 , xa5 , Xa10 , Xa23 and xa25 homologous fragments. These results along with phenotypic resistance spectrum supported that these accessions carried nine resistance homologous genes. Only one accession (Qishanggu_Wenshan) carried the Xa7 resistance gene. We also found that some resistant rice landraces, especially Xilandigu_Baoshan, and Laoyaling_Lincang without the above resistance genes, which mediated broad spectrum resistance to multiple Xoo strains, were identified as potential sources for breeding rice lines resistance to BB.

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

Exploring spatial distributions of increments in soil heavy metals and their relationships with environmental factors using GWR - Hao Li; Peihong Fu; Yong Yang; Xue Yang; Hongjie Gao; Ke Li (Stochastic Environmental Research and Risk Assessment, 2021)

USP18 promotes the growth in hemangiomas by regulating PI3K/AKT pathway - Huan Ke; Xiang Ma; Ying Zeng; Jingjing Lu; Guili Fu (Molecular & Cellular Toxicology, 2021)

Study of pollutant accumulation characteristics and microbial community impact at three bioretention facilities - Ya-jiao Li; Heng Fu; Jing-yu Zhang; Zhao-xin Zhang; Jia-ke Li (Environmental Science and Pollution Research, 2021)

The contrasting relationships of relative humidity with influenza A and B in a humid subtropical region - Qian Wu; Jun He; Wen-Yan Zhang; Ke-Fu Zhao; Jing Jin; Jun-Ling Yu; Qing-Qing Chen; Sai Hou; Meng Zhu; Zhiwei Xu; Hai-Feng Pan (Environmental Science and Pollution Research, 2021)

Taurine improves the differentiation of neural stem cells in fetal rats with intrauterine growth restriction via activation of the PKA-CREB-BDNF signaling pathway - Qiong Fang; Jing Liu; Lang Chen; Qiaobin Chen; Jun Ke; Jiuyun Zhang; Ying Liu; Wei Fu (Metabolic Brain Disease, 2021)

Blocking the JAK2/STAT3 and ERK pathways suppresses the proliferation of gastrointestinal cancers by inducing apoptosis - Xi Wang; Chunyan Dai; Yifei Yin; Lin Wu; Weiyang Jin; Yufei Fu; Zhe Chen; Ke Hao; Bin Lu (Journal of Zhejiang University-SCIENCE B, 2021)

A new chlorine-containing iridoid glycoside from Plantago maxima - Liang-Liang Ma; Lu-Lu Wang; Yue-Feng Zhang; Xiang-Fu Jiang; Xin-Liu Zhu; Ke Pan; Chuan-Xing Wan; Zhong-Bo Zhou (Natural Product Research, 2021)

Lens regeneration: scientific discoveries and clinical possibilities - Yuzhou Gu; Ke Yao; Qiuli Fu (Molecular Biology Reports, 2021)

Genetic diversity and population structure of Tibetan sheep breeds determined by whole genome resequencing - Lei-Lei Li; Shi-Ke Ma; Wei Peng; You-Gui Fang; Hai-Rui Duo; Hong-Yun Fu; Gong-Xue Jia (Tropical Animal Health and Production, 2021)

Characterization of ZmCOLD1, novel GPCR-Type G Protein genes involved in cold stress from Zea mays L. and the evolution analysis with those from other species - Ya-Nan Jin; Zhen-hai Cui; Ke Ma; Jia-Lu Yao; Yan-Ye Ruan; Zhi-Fu Guo (Physiology and Molecular Biology of Plants, 2021)

Optimization inversion analysis of a geo-stress field in a deep mine area: a case study - Qiang Fu; Qin-jie Liu; Ke Yang (Arabian Journal of Geosciences, 2021)

Infestation and distribution of gamasid mites on Himalayan field rat (Rattus nitidus) in Yunnan Province of Southwest China - Rong Xiang; Xian-Guo Guo; Cheng-Fu Zhao; Rong Fan; Ke-Yu Mao; Zhi-Wei Zhang; Xiao-Bin Huang (Biologia, 2021)

Whether the carbon emission from green roofs can be effectively mitigated by recycling waste building material as green roof substrate during five-year operation? - Liangqian Fan; Jingting Wang; Xiaoling Liu; Hongbing Luo; Ke Zhang; Xiaoying Fu; Mei Li; Xiaoting Li; Bing Jiang; Jia Chen; Shuzhi Fu; You Mo; et al. (Environmental Science and Pollution Research, 2020)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Ecological analysis of gamasid mites on the body surface of Norway rats (Rattus norvegicus) in Yunnan Province, Southwest China - Zhe Liu; Xian-Guo Guo; Rong Fan; Cheng-Fu Zhao; Ke-Yu Mao; Zhi-Wei Zhang; Yue Zhao (Biologia, 2020)

Albian–Cenomanian A-type granite-related Ag–Pb–Zn veins in the central Yidun Terrane, SW China: constraints from the Xiasai deposit - Yan-Jun Li; Jun-Hao Wei; Jun Tan; Le-Bing Fu; Huan Li; Kun-Jia Ke (Mineralium Deposita, 2020)

Evoked-potential audiogram variability in a group of wild Yangtze finless porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhi-Tao Wang; Jiao Li; Peng-Xiang Duan; Zhi-Gang Mei; Fu-Qiang Niu; Tomonari Akamatsu; Pei-Yu Lei; Lu Zhou; Jing Yuan; Yu-Wei Chen; Alexander Ya Supin; Ding Wang; et al. (Journal of Comparative Physiology A, 2020)

The influence of DEM spatial resolution on landslide susceptibility mapping in the Baxie River basin, NW China - Zhuo Chen; Fei Ye; Wenxi Fu; Yutian Ke; Haoyuan Hong (Natural Hazards, 2020)

Reference Point Based Multi-Objective Optimization of Reservoir Operation: a Comparison of Three Algorithms - Rong Tang; Ke Li; Wei Ding; Yuntao Wang; Huicheng Zhou; Guangtao Fu (Water Resources Management, 2020)

A practicable method to prepare nitrated proteins with peroxynitrite and low concentration of sodium hydroxide - Nan Zhang; Xiaochen Gao; Weijia Zhang; Doaa Higazy; Ke Wang; Zhenfang Fu; Min Cui (Molecular Biology Reports, 2020)

The Mechanism of Mining-Induced Stress Evolution and Ground Pressure Control at Irregular Working Faces in Inclined Seams - Xiaolou Chi; Ke Yang; Qiang Fu; Litong Dou (Geotechnical and Geological Engineering, 2020)

Identification and Expression Pattern Analysis of Bacterial Blight Resistance Genes in Oryza officinalis Wall ex Watt Under Xanthomonas oryzae Pv. oryzae Stress - Chunmiao Jiang; Suqin Xiao; Dingqin Li; Ling Chen; Qiaofang Zhong; Fuyou Yin; Tengqiong Yu; Xue Ke; Dunyu Zhang; Jian Fu; Yue Chen; Bo Wang; et al. (Plant Molecular Biology Reporter, 2019)
Background Bacterial blight (BB) caused by Xanthomonas oryzae Pv. oryzae ( Xoo ) is one of the most serious diseases of rice worldwide. Oryza officinalis Wall ex Watt, harboring abundant genetic diversity and disease resistance features, are important resources of exploring resistance genes with broad-spectrum resistance to BB. However, the molecular mechanisms and genes of BB resistance in O. officinalis have been rarely explored. Results Here, the BB resistance of four different origin O. officinalis populations in Yunnan were identified by seven representative hypervirulent Xoo races, which exhibited different BB resistance among four populations, in which the BB resistance of the Gengma_Lincang population was the strongest. In addition, the pathogenetic ability of seven Xoo races to O. officinalis was different in that the pathogenicity of PXO99 was stronger than that of C5. There were no remarkable differences in leaf microstructures among four O. officinalis populations, revealing the differences in resistance of four O. officinalis to BB are caused by the endogenous resistance genes. Furthermore, our results proved that there were no nine cloned BB resistance genes in four populations but possessed dominant Xa5 , dominant Xa13 , and recessive xa3/xa26 homologous alleles of xa5 , xa13 , and Xa3 / Xa26 resistance genes. These three homologous genes were isolated and cloned from four populations and named OoXa5 , OoXa13 , and Ooxa3 / xa26 . The expression profile revealed that the expression levels of OoXa13 and Ooxa3/xa26 were significantly down-regulated under PXO99 and C5 stress, especially in the Gengma_Lincang population, suggesting the O. officinalis might enhance BB resistance by down-regulating the expression level of OoXa13 and Ooxa3 / xa26 . Conclusion The BB resistance genes of O. officinalis had its own characteristics by expression pattern and BLAST analysis of OoXa5 , OoXa13 , and Ooxa3 / xa26 , which indicated that there might be new genes or molecular mechanism of BB resistance in O. officinalis. Our studies provided a solid foundation and reference for revealing the molecular mechanism of BB resistance in O. officinalis .

Microsatellite records for volume 11, issue 3 - Pengfei Hu; Hao-Xiang Liu; Ying Pan; Yan-Fu Qu; Xueqi Tian; Ke-Xin Wang; Yu-Heng Wei; Xue-Ping Wu; Xiumei Xing; Zhengyi Zhang; Pei Zhao; Yu-Tian Zhao; et al. (Conservation Genetics Resources, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

Rice OsPEX1, an extensin-like protein, affects lignin biosynthesis and plant growth - Shanwen Ke; Xin Luan; Jiayan Liang; Yu-Hung Hung; Tzung-Fu Hsieh; Xiang-Qian Zhang (Plant Molecular Biology, 2019)

Trichoderma affects the physiochemical characteristics and bacterial community composition of saline–alkaline maize rhizosphere soils in the cold-region of Heilongjiang Province - Jian Fu; Yao Xiao; Yu-feng Wang; Zhi-hua Liu; Ke-jun Yang (Plant and Soil, 2019)

Improving seed germination and oil contents by regulating the GDSL transcriptional level in Brassica napus - Li-Na Ding; Xiao-Juan Guo; Ming Li; Zheng-Li Fu; Su-Zhen Yan; Ke-Ming Zhu; Zheng Wang; Xiao-Li Tan (Plant Cell Reports, 2019)

A New Cable-Truss Structure for Roadway Driving Next to Goaf - Yong-qiang Zhao; Fu-lian He; Jing-ke Wu (Geotechnical and Geological Engineering, 2019)

Overexpression of two cold-responsive ATAF-like NAC transcription factors from fine-stem stylo (Stylosanthes guianensis var. intermedia) enhances cold tolerance in tobacco plants - Peng-Lin Zhan; Shan-Wen Ke; Pan-Yu Zhang; Cong-Cong Zhou; Bei-Ling Fu; Xiang-Qian Zhang; Tian-Xiu Zhong; Shu Chen; Xin-Ming Xie (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Saikosaponin-d inhibits proliferation by up-regulating autophagy via the CaMKKβ–AMPK–mTOR pathway in ADPKD cells - Weiwei Shi; Dechao Xu; Junhui Gu; Cheng Xue; Bo Yang; Lili Fu; Shuwei Song; Dongmei Liu; Wei Zhou; Jiayi Lv; Ke Sun; Meihan Chen; et al. (Molecular and Cellular Biochemistry, 2018)

A novel method for predicting cadmium concentration in rice grain using genetic algorithm and back-propagation neural network based on soil properties - Yi Xuan Hou; Hua Fu Zhao; Zhuo Zhang; Ke Ning Wu (Environmental Science and Pollution Research, 2018)

Genesis of the Angeer Yinwula Pb–Zn deposit, Inner Mongolia, China: constraints from fluid inclusions, C–H–O–S–Pb isotope systematics, and zircon U–Pb geochronology - Han-Lun Liu; Yi Han; Ke-Yong Wang; Wen Li; Jian Li; Wen-Yan Cai; Li-Juan Fu (Arabian Journal of Geosciences, 2018)

Analysis of a broad range of perfluoroalkyl acids in accipiter feathers: method optimization and their occurrence in Nam Co Basin, Tibetan Plateau - Yili Li; Ke Gao; Bu Duo; Guoshuai Zhang; Zhiyuan Cong; Yan Gao; Jianjie Fu; Aiqian Zhang; Guibin Jiang (Environmental Geochemistry and Health, 2018)

LC–MS/MS-Based Metabolome Analysis of Biochemical Pathways Altered by Food Limitation in Larvae of Ivory Shell, Babylonia areolata - Jingqiang Fu; Minghui Shen; Yawei Shen; Wengang Lü; Miaoqin Huang; Xuan Luo; Jinjin Yu; Caihuan Ke; Weiwei You (Marine Biotechnology, 2018)

miR-155 inhibits the formation of hypertrophic scar fibroblasts by targeting HIF-1α via PI3K/AKT pathway - Xue Wu; Jun Li; Xuekang Yang; Xiaozhi Bai; Jihong Shi; Jianxin Gao; Yan Li; Shichao Han; Yijie Zhang; Fu Han; Yang Liu; Xiaoqiang Li; et al. (Journal of Molecular Histology, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Periodic Variation of AAK1 in an Aβ1–42-Induced Mouse Model of Alzheimer’s Disease - Xue Fu; Meiling Ke; Weihua Yu; Xia Wang; Qian Xiao; Min Gu; Yang Lü (Journal of Molecular Neuroscience, 2018)

Crystal structure of Psb27 from Arabidopsis thaliana determined at a resolution of 1.85 Å - Cheng Xingxing; Liu Jiuyang; Zhang Huan; Li Fudong; Zhang Shuya; Xu Min; Ruan Ke; Wang Yuhua; Fu Aigen (Photosynthesis Research, 2018)

Alpha-7 Nicotinic Receptor Signaling Pathway Participates in the Neurogenesis Induced by ChAT-Positive Neurons in the Subventricular Zone - Jianping Wang; Zhengfang Lu; Xiaojie Fu; Di Zhang; Lie Yu; Nan Li; Yufeng Gao; Xianliang Liu; Chunmao Yin; Junji Ke; Liyuan Li; Mengmeng Zhai; et al. (Translational Stroke Research, 2017)

Molecular cloning, characterization, and promoter analysis of the isochorismate synthase (AaICS1) gene from Artemisia annua - Lu-yao Wang; Ying Zhang; Xue-qing Fu; Ting-ting Zhang; Jia-wei Ma; Li-da Zhang; Hong-mei Qian; Ke-xuan Tang; Shan Li; Jing-ya Zhao (Journal of Zhejiang University-SCIENCE B, 2017)

Exposure of Eocanthecona furcellata (Hemiptera: Pentatomidae) nymphs and adults to high temperatures induces an aestivo-hibernal egg diapause: a strategy for surviving hot summers - Jian Wen; Ke-Wei Chen; Lang Fu; Yigen Chen (Applied Entomology and Zoology, 2017)

A naturally occurring conditional albino mutant in rice caused by defects in the plastid-localized OsABCI8 transporter - Xiuyu Zeng; Ran Tang; Herong Guo; Shanwen Ke; Bin Teng; Yu-Hung Hung; Zhenjiang Xu; Xin-Ming Xie; Tzung-Fu Hsieh; Xiang-Qian Zhang (Plant Molecular Biology, 2017)

Identification of novel polymorphic microsatellite loci in the endangered Chinese sucker (Myxocyprinus asiaticus) - NIAN XU; DONG-MEI XU; YAN-FU QUE; FANG SHI; MEI-HUA XIONG; KE SHAO; WEI-TAO LI; BIN ZHU; ZHONG YANG (Journal of Genetics, 2016)

Modeling daily reference ET in the karst area of northwest Guangxi (China) using gene expression programming (GEP) and artificial neural network (ANN) - Sheng Wang; Zhi-yong Fu; Hong-song Chen; Yun-peng Nie; Ke-lin Wang (Theoretical and Applied Climatology, 2016)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Arctic sea ice thickness changes in terms of sea ice age - Haibo Bi; Min Fu; Ke Sun; Yilin Liu; Xiuli Xu; Haijun Huang (Acta Oceanologica Sinica, 2016)

Multiple Effect of APOE Genotype on Clinical and Neuroimaging Biomarkers Across Alzheimer’s Disease Spectrum - Ying Liu; Lan Tan; Hui-Fu Wang; Yong Liu; Xiao-Ke Hao; Chen-Chen Tan; Teng Jiang; Bing Liu; Dao-Qiang Zhang; Jin-Tai Yu (Molecular Neurobiology, 2016)

Voluntary action and tactile sensory feedback in the intentional binding effect - Ke Zhao; Li Hu; Fangbing Qu; Qian Cui; Qiuhong Piao; Hui Xu; Yanyan Li; Liang Wang; Xiaolan Fu (Experimental Brain Research, 2016)

Mapping the vegetation distribution of the permafrost zone on the Qinghai-Tibet Plateau - Zhi-wei Wang; Qian Wang; Lin Zhao; Xiao-dong Wu; Guang-yang Yue; De-fu Zou; Zhuo-tong Nan; Guang-yue Liu; Qiang-qiang Pang; Hong-bing Fang; Tong-hua Wu; Jian-zong Shi; et al. (Journal of Mountain Science, 2016)

The Application of a Water Rights Trading Model Based on two-Stage Interval-Parameter Stochastic Programming - Qiang Fu; Ke Zhao; Dong Liu; Qiuxiang Jiang; Tianxiao Li; Changhong Zhu (Water Resources Management, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

Two-Stage Interval-Parameter Stochastic Programming Model Based on Adaptive Water Resource Management - Qiang Fu; Ke Zhao; Dong Liu; Qiuxiang Jiang; Tianxiao Li; Changhong Zhu (Water Resources Management, 2016)

Effects of ethylene on photosystem II and antioxidant enzyme activity in Bermuda grass under low temperature - Zhengrong Hu; Jibiao Fan; Ke Chen; Erick Amombo; Liang Chen; Jinmin Fu (Photosynthesis Research, 2016)

The association between diurnal temperature range and childhood bacillary dysentery - Li-ying Wen; Ke-fu Zhao; Jian Cheng; Xu Wang; Hui-hui Yang; Ke-sheng Li; Zhi-wei Xu; Hong Su (International Journal of Biometeorology, 2016)

Internal wave parameters retrieval from space-borne SAR image - Kaiguo Fan; Bin Fu; Yanzhen Gu; Xingxiu Yu; Tingting Liu; Aiqin Shi; Ke Xu; Xilin Gan (Frontiers of Earth Science, 2015)

Adaptive Allocation Modeling for a Complex System of Regional Water and Land Resources Based on Information Entropy and its Application - Kun Cheng; Qiang Fu; Xi Chen; Tianxiao Li; Qiuxiang Jiang; Xiaosong Ma; Ke Zhao (Water Resources Management, 2015)

The Effect of Continuous Sedation Therapy on Immunomodulation, Plasma Levels of Antioxidants, and Indicators of Tissue Repair in Post-Burn Sepsis Patients - Li Chen; Ke Meng; Wei Su; Yanjie Fu (Cell Biochemistry and Biophysics, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Rifampicin Loaded Mannosylated Cationic Nanostructured Lipid Carriers for Alveolar Macrophage-specific Delivery - Xu Song; Qing Lin; Ling Guo; Yao Fu; Jianfeng Han; Huan Ke; Xun Sun; Tao Gong; Zhirong Zhang (Pharmaceutical Research, 2015)

Substrate specificity and biochemical characterization of an adenylation domain from an obligate marine actinomycete - Xiao Shu; Yanling Ma; Chong Lu; Ming Lei; Yanli Liu; Ke Liu; Guomei Xiong; Sisi Xia; Zhijuan Zhao; Wenkai Luo; Qiao Fu; Chao Qi (Biotechnology Letters, 2015)

Nd(III)-Induced Rice Mitochondrial Dysfunction Investigated by Spectroscopic and Microscopic Methods - Cai-Fen Xia; Long Lv; Xin-You Chen; Bo-Qiao Fu; Ke-Lin Lei; Cai-Qin Qin; Yi Liu (The Journal of Membrane Biology, 2015)

Clinical effect of postconditioning in ST-elevation myocardial infarction patients treated with primary percutaneous coronary intervention: a meta-analysis of randomized controlled trials - Xian-qing Hu; Jian Cheng; Biao Tang; Zhong-heng Zhang; Ke Huang; Yi-ping Yang; Yan-yan Mao; Ming Zhong; Shen-wen Fu (Journal of Zhejiang University-SCIENCE B, 2015)

High correlation between thermotolerance and photosystem II activity in tall fescue - Ke Chen; Xiaoyan Sun; Erick Amombo; Qing Zhu; Zhuangjun Zhao; Liang Chen; Qingguo Xu; Jinmin Fu (Photosynthesis Research, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Gas drainage efficiency: an input–output model for evaluating gas drainage projects - Fu-bao Zhou; Xin-xin Wang; Ying-ke Liu (Natural Hazards, 2014)

Characteristics of Rocky Basin Structure of Yongshu Reef in the Southern South China Sea - Qing-Shan Meng; Ke-Fu Yu; Ren Wang; Yue Qin; Hou-Zhen Wei; Xin-Zhi Wang (Marine Georesources & Geotechnology, 2014)

Toxicokinetic study of pyrrole adducts and its potential application for biological monitoring of 2,5-hexanedione subacute exposure - Hong-Yin Yin; Ying Guo; Fu-Yong Song; Tao Zeng; Ke-Qin Xie (International Archives of Occupational and Environmental Health, 2014)

MiR-15a-16 represses Cripto and inhibits NSCLC cell progression - Feng Chen; Shi-ke Hou; Hao-jun Fan; Ying-fu Liu (Molecular and Cellular Biochemistry, 2014)

Characterization of OsDREB6 responsive to osmotic and cold stresses in rice - Ya-Guang Ke; Zhi-Jun Yang; Shun-Wu Yu; Tian-Fei Li; Jin-Hong Wu; Huan Gao; Ya-Ping Fu; Li-Jun Luo (Journal of Plant Biology, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

Influence of Electromagnetic Signal of Antibiotics Excited by Low-Frequency Pulsed Electromagnetic Fields on Growth of Escherichia coli - Yin-Lung Ke; Fu-Yu Chang; Ming-Kun Chen; Shun-Lai Li; Ling-Sheng Jang (Cell Biochemistry and Biophysics, 2013)

Alleviation of heat damage to photosystem II by nitric oxide in tall fescue - Ke Chen; Liang Chen; Jibiao Fan; Jinmin Fu (Photosynthesis Research, 2013)

Geology, mineralization, and geochronology of the Qianhe gold deposit, Xiong’ershan area, southern North China Craton - Ke-Fei Tang; Jian-Wei Li; David Selby; Mei-Fu Zhou; Shi-Jian Bi; Xiao-Dong Deng (Mineralium Deposita, 2013)

SCY1-like 1 binding protein 1 (SCYL1-bp1) interacts with p53-induced RING H2 protein (Pirh2) after traumatic brain injury in rats - Jian Chen; Feihui Zou; Hongran Fu; Hui Mao; Mingjie Gong; Lanchun Ni; Xide Xu; Jinlong Shi; Kaifu Ke; Maohong Cao; Fei Zhou; Wei Shi (Journal of Molecular Histology, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

Flexible change and cooperation between mitochondrial electron transport and cytosolic glycolysis as the basis for chilling tolerance in tomato plants - Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; Yang-Wen-Ke Liao; Xiao-Jian Xia; Yan-Hong Zhou; Rong-Qing Wang; Zhi-Xiang Chen; Jing-Quan Yu (Planta, 2013)

Erratum to: Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2013)

Increased expression of actin filament-stabilizing protein tropomyosin after rat traumatic brain injury - Xinmin Wu; Hongran Fu; Feihui Zou; Wei Jin; Ting Xu; Peipei Gong; Jian Xu; Yaohua Yan; Gang Cui; Kaifu Ke; Yilu Gao; Chunfeng Liu; et al. (Journal of Molecular Histology, 2013)

Candida sanyaensis sp. nov., an ascomycetous yeast species isolated from soil - Feng-Li Hui; Qiu-Hong Niu; Tao Ke; Ying-Xia Li; Ching-Fu Lee (Antonie van Leeuwenhoek, 2013)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Full gravity gradient tensors from vertical gravity by cosine transform - Fu-Yu Jiang; Yan Huang; Ke Yan (Applied Geophysics, 2012)

Structural determination of two new triterpenoid saponins acylated with monoterpenic acid from Gymnocladus chinensis Baill. - Wen Qi; Dan Yuan; Lian-Mei Yang; Ke-Hui Xie; Tian-Zhi Cai; Rong Yang; Hong-Zheng Fu (Natural Product Research, 2012)

Characterization of interploid hybrids from crosses between Brassica juncea and B. oleracea and the production of yellow-seeded B. napus - Jing Wen; Lixia Zhu; Liping Qi; Hongmei Ke; Bin Yi; Jinxiong Shen; Jinxing Tu; Chaozhi Ma; TingDong Fu (Theoretical and Applied Genetics, 2012)

Cyclic AMP Response Element Modulator-1 (CREM-1) Involves in Neuronal Apoptosis after Traumatic Brain Injury - Xinmin Wu; Wei Jin; Xiaojuan Liu; Hongran Fu; Peipei Gong; Jian Xu; Gang Cui; Yaohui Ni; Kaifu Ke; Zhiwei Gao; Yilu Gao (Journal of Molecular Neuroscience, 2012)

Increased expression of BAG-1 in rat brain cortex after traumatic brain injury - Ting Xu; Xueqian Wang; Maohong Cao; Xinmin Wu; Yaohua Yan; Hongran Fu; Wei Zhao; Peipei Gong; Kaifu Ke; Xingxing Gu (Journal of Molecular Histology, 2012)

Mutations in isocitrate dehydrogenase 2 accelerate glioma cell migration via matrix metalloproteinase-2 and 9 - Yuejun Fu; Yali Zheng; Ke Li; Rui Huang; Shuhua Zheng; Na An; Aihua Liang (Biotechnology Letters, 2012)

The reduction of reactive oxygen species formation by mitochondrial alternative respiration in tomato basal defense against TMV infection - Yang-Wen-Ke Liao; Kai Shi; Li-Jun Fu; Shuai Zhang; Xin Li; De-Kun Dong; Yu-Ping Jiang; Yan-Hong Zhou; Xiao-Jian Xia; Wu-Sheng Liang; Jing-Quan Yu (Planta, 2012)

Orbilia blumenaviensis and its Arthrobotrys anamorph - Min Qiao; Ying Zhang; Shi-Fu Li; H.-O. Baral; E. Weber; Hong-Yan Su; Jian-Ping Xu; Ke-Qin Zhang; Ze-Fen Yu (Mycological Progress, 2012)

Gold distribution in As-deficient pyrite and telluride mineralogy of the Yangzhaiyu gold deposit, Xiaoqinling district, southern North China craton - Shi-Jian Bi; Jian-Wei Li; Mei-Fu Zhou; Zhan-Ke Li (Mineralium Deposita, 2011)

Estimation of rice neck blasts severity using spectral reflectance based on BP-neural network - Hao Zhang; Hao Hu; Xiao-bin Zhang; Lian-feng Zhu; Ke-feng Zheng; Qian-yu Jin; Fu-ping Zeng (Acta Physiologiae Plantarum, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

COD removal from expanded granular sludge bed effluent using a moving bed biofilm reactor and their microbial community analysis - Bo Fu; Xiaoyi Liao; Rui Liang; Lili Ding; Ke Xu; Hongqiang Ren (World Journal of Microbiology and Biotechnology, 2011)

Analyzing coastal wetland change in the Yancheng National Nature Reserve, China - Chang-Qing Ke; Dong Zhang; Fu-Qiang Wang; Shu-Xing Chen; Christance Schmullius; Wolfgang-Martin Boerner; Hui Wang (Regional Environmental Change, 2011)

Protective effects of adenosine in rabbit sinoatrial node ischemia–reperfusion model in vivo: control of arrhythmia by hyperpolarization-activated cyclic nucleotide-gated (HCN)4 channels - Feng-Xu Yu; Jian-Juan Ke; Yong Fu; Bin Liao; Ying-Kang Shi (Molecular Biology Reports, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

The origin of spongy texture in minerals of mantle xenoliths from the Western Qinling, central China - Ben-Xun Su; Hong-Fu Zhang; Patrick Asamoah Sakyi; Yue-Heng Yang; Ji-Feng Ying; Yan-Jie Tang; Ke-Zhang Qin; Yan Xiao; Xin-Miao Zhao; Qian Mao; Yu-Guang Ma (Contributions to Mineralogy and Petrology, 2011)

RNA interference targeting CITRON can significantly inhibit the proliferation of hepatocellular carcinoma cells - Yinghui Fu; Jian Huang; Ke-Sheng Wang; Xin Zhang; Ze-Guang Han (Molecular Biology Reports, 2011)

Timing and duration of growth hiatuses in mid Holocene massive Porites corals from the northern South China Sea - Ke‐Fu Yu; Jian‐Xin Zhao; Michael G. Lawrence; Yuexing Feng (Journal of Quaternary Science, 2010)
Growth hiatuses in massive corals are usually indicative of past ecological or environmental stresses. Among 37 fossil Porites colonies surveyed from the reef flat of Dadonghai fringing reef at Sanya, Hainan Island, northern South China Sea, seven of them were found to show clear evidence of past mortality, representing a population of ∼19%. Among these samples, two of them (SYO‐13 and SYO‐28) display clear growth hiatuses reflecting mortality followed by subsequent recruitment, and five others exhibit a well‐preserved mortality surface and no subsequent recruitment. The growth hiatuses were dated using high‐precision thermal ionisation mass spectrometry U‐series techniques. The age results suggest all the dated corals formed and died in the mid Holocene. Multiple dates below the growth hiatuses suggest that SYO‐13 and SYO‐28 died at 6298 ± 11 and 6929 ± 19 a BP (i.e. years before AD 1950), respectively. Multiple dates above the growth hiatuses indicate that growth in SYO‐13 and SYO‐28 resumed at 6257 ± 14 and 6898 ± 20 a BP, respectively. The calculated durations of growth hiatuses are therefore 41 ± 18 a for SYO‐13 and 31 ± 28 a for SYO‐28, respectively, implying growth resumed within decades after the mortality events. U‐series dating of four other samples with dead heads suggests that they died at 6035 ± 53, 6059 ± 23, 6127 ± 22 and 6474 ± 24 a BP, respectively. In addition, using solution inductively coupled plasma mass spectrometry (ICP‐MS), monthly resolution Sr/Ca and Mg/Ca ratios were determined for the annual growth bands below and above the growth hiatuses for three of the dated samples. The Sr/Ca and Mg/Ca profiles indicate that the three corals probably died in different seasons (from spring to autumn), and the mortality appears to be unrelated to anomalous sea surface temperature‐induced bleaching. Copyright © 2010 John Wiley & Sons, Ltd.

Spatial Characteristics and Major Sources of Polycyclic Aromatic Hydrocarbons from Soil and Respirable Particulate Matter in a Mega-City, China - Shan Fu; Zhong-Zhi Yang; Ke Li; Xiao-Bai Xu (Bulletin of Environmental Contamination and Toxicology, 2010)

Characterization of microsatellite DNA markers in the Emei moustache toads (Leptobrachium boringii) - Ke Bi; Duncan Deng; M. Kathrine A. Crosby; Jinzhong Fu (Conservation Genetics, 2010)

The metabolic responses and acid–base status after feeding, exhaustive exercise, and both feeding and exhaustive exercise in Chinese catfish (Silurus asotus Linnaeus) - Ke-Gui Li; Zhen-Dong Cao; Jiang-Lan Peng; Shi-Jian Fu (Journal of Comparative Physiology B, 2010)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

Digenean parasites of Chinese marine fishes: a list of species, hosts and geographical distribution - Sheng-fa Liu; Wen-feng Peng; Peng Gao; Ming-jun Fu; Han-zhou Wu; Ming-ke Lu; Ji-qing Gao; Jun Xiao (Systematic Parasitology, 2010)

Undisturbed Strata Succession Sampling Technology and the Engineering Geological Characteristics of an Atoll in the Southern South China Sea - Qing-Shan Meng; Ren Wang; Ke-Fu Yu; Ming-Jian Hu; Xin-Zhi Wang; Chao Yang (Marine Georesources & Geotechnology, 2009)

Frequent mitochondrial gene introgression among high elevation Tibetan megophryid frogs revealed by conflicting gene genealogies - WEI CHEN; KE BI; JINZHONG FU (Molecular Ecology, 2009)
Historical mitochondrial introgression causes differences between a species’ mitochondrial gene genealogy and its nuclear gene genealogy, making tree‐based species delineation ambiguous. Using sequence data from one mitochondrial gene (cytochrome b ) and three nuclear genes (introns), we examined the evolutionary history of four high elevation Tibetan megophryid frog species, Scutiger boulengeri , Scutiger glandulatus , Scutiger mammatus and Scutiger tuberculatus . The three nuclear genes shared a similar history but the mitochondrial gene tree suggested a drastically different evolutionary scenario. The conflicts between them were explained by multiple episodes of mitochondrial introgression events via historical interspecific hybridization. ‘Foreign’ mitochondrial genomes might have been fixed in populations and extended through a large portion of the species’ distribution. Some hybridization events were probably as old as 10 Myr, while others were recent. An F 1 hybrid was also identified. Historical hybridization events among the four species appeared to be persistent and were not restricted to the period of Pleistocene glaciation, as in several other well‐studied cases. Furthermore, hybridization involved several species and occurred in multiple directions, and there was no indication of one mitochondrial genome being superior to others. In addition, incomplete lineage sorting resulting from budding speciation may have also explained some discrepancies between the mitochondrial DNA and nuclear gene trees. Combining all evidences, the former ‘ Scutiger mammatus ’ appeared to be two species, including a new species. With the availability of a wide range of highly variable nuclear gene markers, we recommend using a combination of mitochondrial gene and multiple nuclear genes to reveal a complete species history.

Generation of a stable mammalian cell line for simultaneous expression of multiple genes by using 2A peptide-based lentiviral vector - Tao Hu; Qiong Fu; Ping Chen; Ke Zhang; Deyin Guo (Biotechnology Letters, 2009)

Inhibition on Hepatitis B virus in vitro of recombinant MAP30 from bitter melon - Jian Ming Fan; Qiao Zhang; Jun Xu; Sha Zhu; Tao Ke; De Fu Gao; Yu Bao Xu (Molecular Biology Reports, 2009)

Determination of soluble solid content and acidity of loquats based on FT-NIR spectroscopy - Xia-ping Fu; Jian-ping Li; Ying Zhou; Yi-bin Ying; Li-juan Xie; Xiao-ying Niu; Zhan-ke Yan; Hai-yan Yu (Journal of Zhejiang University-SCIENCE B, 2009)

Phenotypic diversity of the big seed type subcollection of wild soybean (Glycine soja Sieb. et Zucc.) in China - Ke-Jing Wang; Xiang-Hua Li; Fu-Shan Li (Genetic Resources and Crop Evolution, 2008)

Genealogical relationships of southern Ontario polyploid unisexual salamanders (genus Ambystoma) inferred from intergenomic exchanges and major rDNA cytotypes - Ke Bi; James P. Bogart; Jinzhong Fu (Chromosome Research, 2008)

Genealogical relationships of southern Ontario polyploid unisexual salamanders (genus Ambystoma) inferred from intergenomic exchanges and major rDNA cytotypes - Ke Bi; James P. Bogart; Jinzhong Fu (Chromosome Research, 2008)

Expression of a grape calcium-dependent protein kinase ACPK1 in Arabidopsis thaliana promotes plant growth and confers abscisic acid-hypersensitivity in germination, postgermination growth, and stomatal movement - Xiang-Chun Yu; Sai-Yong Zhu; Gui-Feng Gao; Xiao-Jing Wang; Rui Zhao; Ke-Qin Zou; Xiao-Fang Wang; Xiao-Yan Zhang; Fu-Qing Wu; Chang-Cao Peng; Da-Peng Zhang (Plant Molecular Biology, 2007)

Neuroprotective effects of safflor yellow B on brain ischemic injury - Chaoyun Wang; Dalei Zhang; Guisheng Li; Juntian Liu; Jingwei Tian; Fenghua Fu; Ke Liu (Experimental Brain Research, 2007)

Screen p53 mutations in hepatocellular carcinoma by FASAY: A novel splicing mutation - Xiao-mo Wu; Jing-geng Fu; Wang-zhong Ge; Jiang-yan Zhu; Jun-yong Wang; Wei Zhang; Wei Qian; Ke-ke Huo (Journal of Zhejiang University-SCIENCE B, 2007)

Successful implantation of intravenously administered stem cells correlates with severity of inflammation in murine myocarditis - Sohail Malek; Emel Kaplan; Ju-Feng Wang; Qingen Ke; Jamal S. Rana; Yu Chen; Bilal G. Rahim; Ma Li; Qin Huang; Yong-Fu Xiao; Freek W. A. Verheugt; James P. Morgan; et al. (Pflügers Archiv - European Journal of Physiology, 2006)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

Topaz–albite granites and rare-metal mineralization in the Limu District, Guangxi Province, southeast China - Jin-Chu Zhu; Ren-Ke Li; Fu-Chun Li; Xiao-Lin Xiong; Feng-Ying Zhou; Xiao-Long Huang (Mineralium Deposita, 2001)

Concept, distribution law and formation machanism of inland saline-alkaline wetland - Guang-you Sun; Xin-zheng Luo; Fu-ke Yi; Xiao-ping Zhang (Chinese Geographical Science, 2000)

Finding spatial regularity in mosaic landscapes: two methods integrated - Ke-Ming Ma; Bo-Jie Fu; Xu-Dong Guo; Hua-Feng Zhou (Plant Ecology, 2000)

Biology and life history of Dabry's sturgeon, Acipenser dabryanus, in the Yangtze River - Ping Zhuang; Fu'en Ke; Qiwei Wei; Xuefu He; Yuji Cen (Environmental Biology of Fishes, 1997)

Biology, fisheries, and conservation of sturgeons and paddlefish in China - Qiwei Wei; Fu'en Ke; Jueming Zhang; Ping Zhuang; Junde Luo; Rueqiong Zhou; Wenhua Yang (Environmental Biology of Fishes, 1997)